Sealing film and sealing composition for sealing microcells of electro-optical devices

The deficiencies of prior art water-based sealing compositions in electro-optical devices are solved by using a combination of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, polyurethane and rheology modifier, It achieves the effects of improving barrier properties, reducing moisture absorption and improving electro-optical performance.

CN119343400APending Publication Date: 2025-01-21E INK CORP

Patent Information

Application Number
CN202380045787.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-06-23
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively form an aqueous sealing composition with fewer defects, improves barrier to non-polar fluids, reduces hygroscopic properties, and improves electro-optical properties, and is used in the sealing film of electro-optical devices.

Method used

Adopt a combination of polymer (alcohol) polymer or polymer (ethylene-co--ethylene) sync, polyurethane, and flow modifiers. Aythne or alkali -expanded emulsion polymer.

Benefits of technology

A sealing film with less defects and good electrophoretic performance is formed, which improves the obstruction of non -polar fluid, reduces hygroscopicity, and improves the total surface energy and interface tension of the sealing membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343400A_ABST
    Figure CN119343400A_ABST
Patent Text Reader

Abstract

The present invention relates to an aqueous sealing composition comprising a combination of a polymer-poly (vinyl alcohol) homopolymer or poly (vinyl alcohol-co-ethylene) copolymer, a polyurethane, and a rheology modifier in an aqueous carrier. The aqueous sealing composition may be used to form a low defect sealing film in an electro-optical device having an electro-optical material layer comprising (a) a plurality of microcells filled with charged particles and a non-polar fluid, and (b) a sealing film, where the electro-optical material layer is disposed between two electrode layers. The corresponding electro-optical device shows good electro-optical performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 357,745, filed on July 1, 2022. The entire contents of any patent, published application, or other published work referenced herein are incorporated by reference. Field of the Invention

[0003] The present invention relates to a sealing film that can be used in electro-optical devices such as electrophoretic displays. The sealing film comprises a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer, a polyurethane and a rheology modifier selected from a hydrophobically modified ethoxylated urethane and an alkali swellable emulsion polymer. Background of the Invention

[0005] The term "electro-optical" as applied to a material, device or display is used herein in its conventional sense in the imaging arts to refer to a material having a first display state and a second display state that differ in at least one optical property, the material changing from its first display state to its second display state by application of an electric field to the material. While the optical property is typically a color perceptible to the human eye, it may be another optical property such as optical transmission, reflection, luminescence, or, in the case of a display intended for machine reading, a false color in the sense of a change in reflectivity of electromagnetic wavelengths outside the visible range.

[0006] The terms "bistable" and "bistability" are used herein in their conventional sense in the art to refer to a display that includes display elements having first and second display states that differ in at least one optical property, and such that after any given element has been driven to assume its first or second display state by means of an addressing pulse of finite duration, that state will persist after termination of the addressing pulse for at least several times, e.g., at least four times, the minimum duration of the addressing pulse required to change the state of the display element. Some particle-based electrophoretic displays with grayscale capability are shown in U.S. Pat. No. 7,170,670 to be stable not only in their extreme black and white states, but also in their intermediate gray states, and some other types of electro-optical devices are likewise. This type of display is properly referred to as "multistable" rather than bistable, but for convenience, the term "bistable" may be used herein to cover both bistable and multistable displays.

[0007] One type of electro-optical device that has been the subject of intensive research and development for several years is a particle-based electrophoretic display, in which a plurality of charged particles move through a fluid under the influence of an electric field. When compared to liquid crystal displays, electrophoretic displays may have the properties of good brightness and contrast, wide viewing angles, state bistability, and low power consumption.

[0008] A number of patents and applications assigned to or in the name of the Massachusetts Institute of Technology (MIT), E Ink Corporation, E Ink California, LLC and related companies describe various technologies for encapsulated and microcell electrophoretic media and other electro-optical media. Encapsulated electrophoretic media contain a plurality of small capsules, each of which itself includes an inner phase containing particles that electrophoretically move in a fluid medium, and a capsule wall surrounding the inner phase. Typically, the capsules themselves are held in a polymer binder to form a coherent layer between two electrodes. In a microcell electrophoretic display, the charged particles and fluid are not encapsulated in microcapsules, but are retained in a plurality of cavities formed in a carrier medium, which is typically a polymer film.

[0009] The technologies described in these patents and applications include:

[0010] (a) electrophoretic particles, fluids, and fluid additives; see, e.g., U.S. Pat. Nos. 7,002,728 and 7,679,814;

[0011] (b) capsules, binders and packaging methods; see, e.g., U.S. Pat. Nos. 6,922,276 and 7,411,719;

[0012] (c) microcell structures, wall materials, and methods of forming microcells; see, e.g., U.S. Pat. Nos. 7,072,095 and 9,279,906;

[0013] (d) methods for filling and sealing microlocations; see, e.g., U.S. Patent Nos. 7,144,942; 7,005,468; and 7,715,088; and U.S. Patent Application Publication Nos. 2004-0120024 and 2004-0219306;

[0014] (e) Films and subassemblies containing electro-optical materials; see, e.g., U.S. Pat. Nos. 6,982,178 and 7,839,564;

[0015] (f) Backplanes, adhesive layers and other auxiliary layers and methods for displays; see, e.g., U.S. Pat. Nos. 7,116,318 and 7,535,624;

[0016] (g) color formation and color adjustment; see, e.g., U.S. Pat. Nos. 7,075,502 and 7,839,564;

[0017] (h) Methods for driving displays; see, e.g., U.S. Pat. Nos. 7,012,600 and 7,453,445;

[0018] (i) Display applications; see, e.g., U.S. Pat. Nos. 7,312,784 and 8,009,348; and

[0019] (j) Non-electrophoretic displays; as described in U.S. Patent No. 6,241,921 and U.S. Patent Application Publication No. 2015 / 0277160; and applications of packaging and microcell technology other than displays; see, for example, U.S. Patent No. 7,615,325; and U.S. Patent Application Publications Nos. 2015 / 0005720 and 2016 / 0012710.

[0020] The contents of all of the above references are incorporated herein by reference in their entirety.

[0021] Structures with multiple sealed microcells are commercially used in electro-optical devices, wherein the sealed microcells contain a dispersion of charged pigment particles in a non-polar fluid. Microcells are also referred to as microcavities or microcups in the literature. The general process of manufacturing a sealed microcell structure for an electro-optical device includes (a) manufacturing a polymer sheet with multiple microcavities by micro-imprinting, wherein each microcavity has an opening, (b) filling the microcavities with an electrophoretic medium, which is a dispersion of charged pigment particles contained in a non-polar fluid, and (c) sealing the microcavities with an aqueous sealing composition to form a sealing film. The sealed microcavities containing the electrophoretic medium form an electro-optical material layer of the device. The electro-optical material layer is disposed between the front electrode and the rear electrode. Applying an electric field across the electrophoretic medium through these electrodes causes the pigment particles to migrate through the electrophoretic medium, producing an image. The sealing film plays an important role in the function and performance of the device. First, since the sealing film contacts the electrophoretic medium and seals it within the microcavity, it must (1) be virtually insoluble in the nonpolar fluid of the electrophoretic medium and (2) be a good barrier to the nonpolar fluid so that the nonpolar fluid does not diffuse out of the microcell during the life of the device. The poor barrier properties of the sealing film to the nonpolar fluid result in a reduction of the fluid in the electrophoretic medium and sagging of the sealing film. Second, the sealing film must not absorb a large amount of moisture from the environment; that is, it must prevent ambient moisture from entering the electrophoretic medium of the device. Such moisture can have a negative impact on the electro-optical performance of the device. Third, the sealing composition should be applied to the microcell layer to form a sealing film without significant coating defects, because such defects have a negative impact on the electro-optical performance of the corresponding device. Fourth, the sealing film should have mechanical elasticity during the service life of the device. Finally, the sealing film should have an optimal volume resistivity that remains virtually constant over time. The conductive properties of the sealing film are important because, in addition to other components, an electric potential is applied to the device and conducted through the sealing film.

[0022] The technical problem of providing an aqueous sealing composition forming a sealing film with these characteristics is difficult, because different targets may require different formulation strategies. For example, the barrier properties to non-polar fluids generally require more hydrophilic components, and such components absorb more moisture from the environment. In addition, if the sealing film has low conductivity, the operation of the device requires increased power consumption, and too high conductivity can cause image quality degradation due to frosting. Therefore, there is a demand for an aqueous sealing composition forming an optimized sealing film with fewer defects, improved barrier to non-polar fluids, reduced hygroscopicity and improved electro-optical properties. The inventors of the present invention have found that a sealing film composition comprising a combination of poly (vinyl alcohol) homopolymer or poly (vinyl alcohol-co-ethylene) copolymer, polyurethane and rheology modifier provides a sealing film with fewer defects and good electro-optical properties, and the rheology modifier is a hydrophobically modified ethoxylated urethane or an alkali swellable emulsion polymer. SUMMARY OF THE INVENTION

[0024] In one aspect, the present invention relates to a sealing film comprising 15 to 60 wt % of a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, 7 to 29 wt % of a polyurethane, and 0.05 to 10 wt % of a rheology modifier, based on the weight of the sealing film. The poly(vinyl alcohol) homopolymer has a degree of hydrolysis of 90 to 99.5%. The poly(vinyl alcohol-co-ethylene) copolymer has a degree of hydrolysis of 90 to 99.5% and an ethylene content of less than 10%. The rheology modifier is selected from a hydrophobically modified ethoxylated urethane and an alkali swellable emulsion polymer. The sealing film may further comprise 0.001 to 5 wt % of a surfactant, based on the weight of the sealing film. The sealing film may comprise 0.01 to 5 wt % of a surfactant, based on the weight of the sealing film, or 0.01 to 2 wt % of a surfactant, based on the weight of the sealing film. The surfactant of the sealing film may be a fluorosurfactant. The sealing film may further comprise 5 to 70 wt % of carbon black based on the weight of the sealing film. The carbon black may have an oil absorption value of less than 100 mL / 100 mg of carbon black measured using the OAN method according to ASTM 2414. The carbon black may have an oil absorption value of less than 70 mL / 100 mg of carbon black measured using the nitrogen adsorption method according to ASTM D 6556. 2 / g total surface area.

[0025] The sealing film may further comprise 4.5 to 25 wt % of a water-soluble ether having a molecular weight of 75 to 5000 Daltons, based on the weight of the sealing film, and optionally comprising a hydroxyl group.

[0026] The total surface energy of the sealing film may be less than 60 mN / m. The interfacial tension between the water-soluble poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane may be less than 2 mN / m. The sealing film may have a surface energy of 10 7 Up to 10 11 Volume resistivity in ohm-cm.

[0027] The polyurethane of the sealing film may be ester polyurethane, polycarbonate polyurethane or a combination thereof. The polyurethane of the sealing film may have a number average molecular weight of 1000 to 2000000 Daltons.

[0028] The poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer of the sealing film may have a number average molecular weight of 1000 to 1000000 Daltons. The poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer of the sealing film may have a degree of hydrolysis of 92% to 99%. The poly(vinyl alcohol-co-ethylene) copolymer of the sealing film may have an ethylene content of less than 9%.

[0029] On the other hand, the present invention relates to an electro-optical device comprising a conductive layer, a microcell layer, a sealing film, an adhesive layer and an electrode layer. The microcell layer comprises a plurality of microcells, each microcell comprising an opening, and each microcell comprising an electrophoretic medium. The electrophoretic medium comprises charged particles in a non-polar carrier. The sealing film of the electro-optical device comprises 15 to 60 wt % of a water-soluble poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer, 7 to 29 wt % of a polyurethane, and 0.05 to 10 wt % of a rheology modifier, based on the weight of the sealing film. The poly(vinyl alcohol) homopolymer has a degree of hydrolysis of 90% to 99.5%. The poly(vinyl alcohol-co-ethylene) copolymer has a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%. The rheology modifier is selected from a hydrophobically modified ethoxylated urethane and an alkali-swellable emulsion polymer. The electrophoretic medium of the electro-optical device may contain at least three types of charged pigment particles, at least one type of charged particles having a color selected from the group consisting of blue, green, red, cyan, magenta and yellow.

[0030] In yet another aspect, the present invention relates to an aqueous sealing composition comprising 15 to 60 wt % of a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, based on the weight of the aqueous sealing composition excluding water, 7 to 29 wt % of a polyurethane, based on the weight of the aqueous sealing composition excluding water, 0.05 to 5 wt % of a rheology modifier, based on the weight of the aqueous sealing composition excluding water, 0.01 to 5 wt % of a surfactant, based on the weight of the aqueous sealing composition excluding water, and 20 to 95 wt % of water, based on the weight of the aqueous sealing composition. The poly(vinyl alcohol) homopolymer has a degree of hydrolysis of 90% to 99.5%. The poly(vinyl alcohol-co-ethylene) copolymer has a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%. The rheology modifier is selected from a hydrophobically modified ethoxylated urethane and an alkali swellable emulsion polymer. The surfactant of the aqueous sealing composition may be a fluorosurfactant.

[0031] The aqueous sealing composition may further comprise 5 to 70 wt % of carbon black based on the weight of the aqueous sealing composition excluding water. The carbon black may have an oil absorption value of less than 100 mL / 100 mg of carbon black measured using the OAN method according to ASTM 2414. The carbon black may have an oil absorption value of less than 70 mL / 100 mg of carbon black measured using the nitrogen adsorption method according to ASTM D 6556. 2 / g total surface area.

[0032] The aqueous sealing composition may further comprise 1.0 to 40 wt % of a water-soluble ether having a molecular weight of 75 to 5000 Daltons (g / mol) and optionally comprising a hydroxyl group, based on the weight of the aqueous sealing composition excluding water.

[0033] The aqueous sealing composition may further comprise 0.1 to 8 wt % of a polyurethane crosslinking agent based on the weight of the aqueous sealing composition excluding water. The polyurethane crosslinking agent is polyisocyanate, polyfunctional polycarbodiimide, polyfunctional aziridine, silane coupling agent, boron / titanium / zirconium-based crosslinking agent or melamine formaldehyde.

[0034] The aqueous sealing composition is -4 The viscosity of the aqueous sealing composition at a shear rate of 1 / s divided by the viscosity of the aqueous sealing composition at a shear rate of 10 2 The viscosity ratio of the viscosity at a shear rate of l / s may be 7 or less. The aqueous sealing composition is -4 The viscosity of the aqueous sealing composition at a shear rate of 1 / s divided by the viscosity of the aqueous sealing composition at a shear rate of 10 2 The viscosity ratio of the viscosity at a shear rate of 1 / s may be 1 to 7. The aqueous sealing composition may have an HB rate index of 0.7 or more. The aqueous sealing composition may have an HB rate index of 0.7 to 1, 0.7 to 0.9, or 0.7 to 2. The aqueous sealing composition may have a thixotropic index of 1.5 or more. The aqueous sealing composition may have a thixotropic index of 1.5 to 3. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The diagram illustrates the structure of a plurality of microcells before they are filled and sealed (side view).

[0037] Figure 2 An example of an electro-optical device including a microcell structure is illustrated (side view).

[0038] Figure 3 An example of a front plane laminate assembly that can be used to form an electro-optical device including a microcell structure is illustrated (side view).

[0039] Figure 4 An example of a double release sheet that can be used to form an electro-optical device including a microcell structure is illustrated (side view).

[0040] Figure 5 A method of manufacturing a micro unit using a roll-to-roll method is shown.

[0041] Fig. 6A and 6B DETAILED DESCRIPTION Microcells are fabricated using photolithographic exposure through a photomask coated with a conductor film of a thermosetting precursor.

[0042] Figure 6C and 6D An alternative embodiment is described in detail in which the microcells are fabricated using photolithography. Figure 6C and 6DIn the embodiment of the present invention, a combination of top and bottom exposure is used, allowing the walls in one lateral direction to be cured by exposure through the top photomask, and the walls in the other lateral direction to be cured by bottom exposure through the opaque base conductor film.

[0043] Figures 7A-7D Diagram illustrating the steps of filling and sealing a microcell array.

[0044] Figure 8 The diagram illustrates the structure of the electro-optical device used to evaluate the electro-optical performance of the aqueous sealing composition embodiments.

[0045] Fig. 9 The diagram illustrates the structure of the electro-optical device used to evaluate the barrier properties of aqueous sealing composition embodiments.

[0046] Figures 10A-10D Microscope images showing microcells evaluated for barrier properties.

[0047] Fig.11 Examples of sealing films corresponding to the dehumidification graded system are shown.

[0048] Fig.12 Examples of sealing films corresponding to the hierarchical grading system are shown.

[0049] Fig.13 Examples of sealing films corresponding to the chatter rating system are shown.

[0050] Fig.14 Examples of sealing films corresponding to the Cloudy Spot Mura grading system are shown.

[0051] Fig.15 Microscopic images of polymer films comprising a combination of poly(vinyl alcohol-co-ethylene) copolymers and polyurethanes having different interfacial tensions are shown. DETAILED DESCRIPTION OF THE INVENTION

[0053] As used herein, "molecular weight" or "MW" refers to weight average molecular weight, unless otherwise indicated. Molecular weight is measured using gel permeation chromatography ("GPC").

[0054] The degree of hydrolysis of a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer is the ratio of the number of moles of vinyl alcohol groups in the polymer to the sum of the number of moles of vinyl alcohol groups and the number of moles of vinyl acetate groups. Thus, in the example of the simplified polyvinyl alcohol formula (Formula I) provided below, the degree of hydrolysis is calculated by Equation 1.

[0055] Degree of hydrolysis = 100 x p / (p+q) Equation 1

[0056] Polyvinyl alcohol manufacturers generally report the degree of hydrolysis of their products, since this parameter affects important physical properties of the polymer, such as the water solubility of the polymer and the water resistance of the corresponding dry film. The degree of hydrolysis of polyvinyl alcohol (homopolymers and copolymers) is determined using a titration method. Details of this method are described in method JIS K 6726 (Japanese Standards Association, 94th edition, October 20, 2017).

[0057]

[0058] The terms "sealing film" and "sealing layer" are synonymous and are used interchangeably when referring to electro-optical devices.

[0059] The terms "adhesive film" and "adhesive layer" are synonymous and may be used interchangeably when referring to electro-optical devices.

[0060] The terms "surfactant", "surfactant (surfactant)" and "wetting agent" are synonymous in this article. "Surfactant" or "surfactant (surfactant)" or "wetting agent" is a substance that can reduce the surface tension of a liquid, the interfacial tension between two liquids, the interfacial tension between a gas and a liquid, and the interfacial tension between a liquid and a solid. Surfactants are generally amphiphilic organic compounds, which means that they contain one or more hydrophobic functional groups (tails) and one or more hydrophilic groups (heads). "Fluorosurfactants" are surfactants having at least one fluorine atom in their molecular structure, more specifically, surfactants having fluorine atoms in the alkyl chain of the surfactant tail. Fluorosurfactants can have more than one fluorine atom in the alkyl chain of the surfactant tail.

[0061] Unless otherwise stated, the disclosed content of the components of the sealing film is calculated as the weight % of the component based on the weight of the sealing film. Unless otherwise stated, the disclosed content of the components of the aqueous sealing composition is calculated as the weight % of the aqueous sealing composition excluding water (except, of course, the disclosed content of water in the aqueous composition).

[0062] A. Microcell Structure

[0063] Figure 1 The structure of a plurality of microcells 100 is illustrated in side view. The illustration shows a plurality of microcells 100 before they are filled and sealed. Each microcell comprises a bottom 101, a wall 102 and an opening 103.

[0064] B. Structure of an electro-optical device including a microcell structure

[0065] Figure 2The diagram illustrates an example of an electro-optical device 200 shown in a side view. The electro-optical device of this example includes a first light-transmitting electrode layer 210, a microcell layer 220, a sealing film 230, an adhesive layer 240, and a second electrode layer 250. The microcell layer includes a plurality of microcells defined by a bottom 101 and a wall 102 of the microcell. Each of the plurality of microcells has an opening 103. Each of the plurality of microcells contains an electrophoretic medium 225, which contains charged particles in a non-polar fluid. The microcells are sealed with a sealing film 230, which spans the openings 102 of the plurality of microcells. The second electrode layer 250 is connected to the sealing film 230 using an adhesive layer 240. Each of the plurality of microcells sealed with the sealing film forms an electro-optical material layer of the electro-optical device 200. An electric field source can connect the first light-transmitting electrode layer 210 and the second electrode layer 250. Application of an electric field across the layer of electrophoretic material causes the charged particles to migrate through the electrophoretic medium, producing an image that can be viewed by an observer viewing from the viewing side 215 of the electro-optical device 200. Figure 2 The first light-transmitting electrode layer 210 and the micro unit layer 220 may be disposed between the first light-transmitting electrode layer 210 and the micro unit layer 220 .

[0066] Figure 2 The illustrated example of an electro-optical device may be formed from a front plane laminate 300, a side view of which illustrates a Figure 3 As shown. The front plane laminate 300 includes a first light-transmitting electrode layer 210, a microcell layer 220, a sealing film 230, an adhesive layer 240, and a release sheet 360. Each of the plurality of microcells contains an electrophoretic medium 225, which contains charged particles in a non-polar fluid. The microcells are sealed with a sealing film 230, which spans the openings of the plurality of microcells. The release sheet 360 is connected to the sealing film 230 using the adhesive layer 240. Removal of the release sheet 360 exposes the surface of the adhesive layer 240, which can be connected to the second electrode layer to form an electro-optical device. The optional bottom layer ( Figure 3 The first light-transmitting electrode layer 210 and the micro unit layer 220 may be disposed between the first light-transmitting electrode layer 210 and the micro unit layer 220 .

[0067] Figure 2 The illustrated example of an electro-optical device may also be formed from a double release sheet 400, the side view of which is shown in FIG. Figure 4As shown. The double release sheet 400 includes a first release sheet 480, a first adhesive layer 470, a microcell layer 220, a sealing film 230, a second adhesive layer 340 and a second release sheet 360. Each of the plurality of microcells contains an electrophoretic medium 225, which contains charged particles in a non-polar fluid. The microcells are sealed with a sealing film 230. The sealing film 230 spans the openings of the plurality of microcells. The first release sheet 480 is connected to the microcell layer 220 using the first adhesive layer 470. The second release sheet 360 is connected to the sealing film 230 using the second adhesive layer 240. Removal of the first release sheet 460 exposes the surface of the first adhesive layer 470, which can be connected to the first light-transmitting electrode layer. Removal of the second release sheet 360 exposes the surface of the second adhesive layer 240, which can be connected to the second electrode layer to form an electro-optical device. The optional bottom layer ( Figure 4 ) may be disposed between the first adhesive layer 470 and the micro unit layer 220 .

[0068] C. Formation of micro-unit structure

[0069] Techniques for constructing microcells. Microcells can be formed by a batch process or by a continuous roll-to-roll process, as disclosed in U.S. Pat. No. 6,933,098. The latter provides a continuous, low-cost, high-throughput manufacturing technology for making compartments for use in a variety of applications including beneficial agent delivery and electrophoretic displays. Figure 5 As illustrated, micro-unit arrays suitable for use in the present invention can be produced using micro-imprinting. The male mold 500 can be placed above the web 504 or below the web 504 (not shown); however, alternative arrangements are possible. For example, see U.S. Pat. No. 7,715,088, which is incorporated herein by reference in its entirety. A conductive substrate can be constructed by forming a conductor film 501 on a polymer substrate, which becomes the backing layer of the device. A composition comprising a thermoplastic, a thermosetting substance, or a precursor thereof is then coated on the conductor film 501. The thermoplastic or thermosetting precursor layer 502 is embossed by a male mold in the form of a roller, plate, or belt at a temperature above the glass transition temperature of the material of the thermoplastic or thermosetting precursor layer 502.

[0070] The thermoplastic or thermosetting precursor layer 502 used to prepare the micro-unit can include multifunctional acrylates or methacrylates, vinyl ethers, epoxides and their oligomers or polymers, etc. The combination of multifunctional epoxides and multifunctional acrylates is also very useful for achieving the desired physical and mechanical properties. Crosslinkable oligomers such as urethane acrylates or polyester acrylates that impart flexibility can be added to improve the flexural resistance of the imprinted micro-units. The composition of the thermoplastic or thermosetting precursor layer 502 can include polymers, oligomers, monomers and additives or only oligomers, monomers and additives. The glass transition temperature (T g ) is usually in the range of about -70°C to about 150°C or about -20°C to about 50°C. Micro-embossing methods are generally carried out at temperatures above T g A heated male mold or a heated housing substrate against which the mold is pressed can be used to control the micro-embossing temperature and pressure.

[0071] like Figure 5 As shown, demoulding can be performed during or after the thermoplastic or thermosetting precursor layer 502 is hardened to reveal the array of microunits 503. The hardening of the thermoplastic or thermosetting precursor layer 502 can be completed by cooling, solvent evaporation, radiation crosslinking, heat or moisture. In the case of a thermosetting precursor layer, curing can be completed by ultraviolet radiation. In this case, as shown in the two figures, ultraviolet rays can be radiated from the bottom or top of the web onto the transparent conductor film. Alternatively, a UV lamp can be placed in the mold. In this case, the mold must be transparent so that ultraviolet light is radiated onto the thermosetting precursor layer through a pre-patterned positive mold. The positive mold can be prepared by any suitable method, such as a diamond turning method or a photoresist method, and then etching or electroplating. The master template for the positive mold can be manufactured by any suitable method, such as electroplating. Using electroplating, a thin layer (generally 200 μm) of a seed metal such as chrome inconel is used. ) sputtering glass substrate. Then the mold is coated with a photoresist layer and exposed to ultraviolet light. A mask is placed between the ultraviolet light source and the photoresist layer. The exposed areas of the photoresist become hardened. Then it is removed by washing the unexposed areas with a suitable solvent. The remaining hardened photoresist is dried and sputtered again with a thin layer of seed metal. Then the master is ready for electroforming. Typical materials for electroforming are nickel cobalt. Alternatively, the master can be made of nickel by electroforming or chemical nickel plating deposition. The mold base is generally about 50 to about 400 microns. The master can also be manufactured using other microengineering techniques, including electron beam writing, dry etching, chemical etching, laser writing or laser interference, as described in "Replication techniques for micro-optics", SPIE Proc. Vol. 3099, pp. 76-82 (1997). Alternatively, the mold can be manufactured using plastic, ceramic or metal by photomechanical processing.

[0072] Before applying the UV-curable resin composition, the mold can be treated with a release agent to help the demoulding process. The UV-curable resin can be degassed before distribution and can optionally contain a solvent. The solvent (if present) evaporates easily. The UV-curable resin is distributed on the male mold by any suitable means, such as coating, dipping, pouring, etc. The distributor can be mobile or fixed. The conductor film is covered with the UV-curable resin. If necessary, pressure can be applied to ensure that the appropriate combination between the resin and the plastic is controlled and the thickness of the micro-unit bottom (base plate) is controlled. Laminating rollers, vacuum molding, pressure devices or any other similar means can be used to apply pressure. If the male mold is metallic and opaque, the plastic substrate is generally transparent to the actinic radiation used to cure the resin. On the contrary, the male mold can be transparent, and the plastic substrate can be opaque to actinic radiation. In order to realize that the molded features are well transferred to the transfer sheet, the conductor film needs to have good adhesion to the UV-curable resin, and the UV-curable resin should have good release properties for the mold surface.

[0073] The microcell array of the present invention generally includes a conductive layer formed by a preformed conductor film such as indium tin oxide (ITO) conductor lines; however, other conductive materials such as silver or aluminum may be used. The conductive layer may be supported by or integrated into a substrate such as polyethylene terephthalate, polyethylene naphthalate, polyarylamide, polyimide, polycycloolefin, polysulfone, epoxy resin and their composites. The conductor film may be coated with a radiation-curable polymer precursor layer. The film and precursor layer are then imagewise exposed to radiation to form a microcell wall structure. After exposure, the precursor material is removed from the unexposed areas, leaving the cured microcell walls bonded to the conductor film / support web. Imagewise exposure may be accomplished by ultraviolet light or other forms of radiation through a photomask to produce an exposed image or predetermined pattern of the radiation-curable material coated on the conductor film. Although not typically required, the mask can be positioned and aligned relative to the conductor film, ie, the ITO lines, so that transparent mask portions are aligned with the spaces between the ITO lines and opaque mask portions are aligned with the ITO material (intended for the microcell floor area).

[0074] Photolithography. Microcells can also be made using photolithography. Photolithography methods for making microcell arrays are Fig. 6A and 5 B is a diagram. Fig. 6A and 6B As shown, the microcell array 600 can be prepared by exposing a radiation-curable material 601a coated on a conductor electrode film 602 by known methods to ultraviolet light (or alternatively other forms of radiation, electron beams, etc.) through a mask 606 to form walls 601b corresponding to the image projected through the mask 606. The base conductor film 602 is preferably mounted on a supporting substrate base web 603, which can include a plastic material.

[0075] exist Fig. 6A In the photomask 606 in FIG. 1 , the dark squares 604 represent opaque areas of the mask 606, and the spaces between the dark squares represent transparent areas 605 of the mask 606. The ultraviolet radiation reaches the radiation-curable material 601a through the transparent areas 605. The exposure is preferably performed directly on the radiation-curable material 601a, i.e., the ultraviolet light does not pass through the supporting substrate base web 603 or the base conductor film 602 (top exposure). For this reason, neither the supporting substrate base web 603 nor the conductor 602 need to be transparent to the ultraviolet light or other radiation wavelengths used.

[0076] like Figure 6BAs shown, the exposed areas become hardened, and then the unexposed areas (protected by the opaque areas 604 of the mask 606) are removed by an appropriate solvent or developer to form microcells 607. The solvent or developer is selected from those commonly used to dissolve radiation-curable materials or reduce the viscosity of radiation-curable materials, such as methyl ethyl ketone (MEK), toluene, acetone, isopropyl alcohol, etc. The preparation of microcells can be similarly accomplished by placing a photomask under the conductor film / support substrate base web, in which case the UV light is radiated through the photomask from the bottom, and the support substrate base web 603 needs to be transparent to the radiation.

[0077] Imagewise exposure. Another alternative method for preparing the microunit array of the present invention by imagewise exposure is Figure 6C and 6D When opaque conductor lines are used, the conductor lines can be used as a photomask for exposure from the bottom. Additional exposure from the top through a second photomask with opaque lines perpendicular to the conductor lines forms durable microcell walls. Figure 6C The diagram illustrates the use of the top and bottom exposure principles to manufacture the microcell array 610 of the present invention. The base conductor film 612 is opaque and line patterned. The radiation-curable material 611a coated on the base conductor film 612 and the substrate 613 is exposed from the bottom through the base conductor film 612 used as a first photomask. A second exposure is performed from the "top" side through a second photomask 616 having a line pattern perpendicular to the base conductor film 612. The spaces 615 between the lines 614 are substantially transparent to ultraviolet light. In this process, the wall material 611b is cured from the bottom up in a lateral orientation and from the top down in a vertical direction, connecting to form an integral microcell 617. As shown in FIG. Fig.6D As shown, the unexposed areas are then removed by a solvent or developer as described above to reveal the microelements 617.

[0078] The microunits may be composed of thermoplastic elastomers that have good compatibility with the microunits and do not interact with the medium. Examples of useful thermoplastic elastomers include ABA and (AB)n type diblock, triblock and multiblock copolymers, wherein A is styrene, α-methylstyrene, ethylene, propylene or norbornene; B is butadiene, isoprene, ethylene, propylene, butylene, dimethylsiloxane or propylene sulfide; wherein A and B cannot be the same. The number n ≥ 1, preferably 1-10. Particularly useful are diblock or triblock copolymers of styrene or α-methylstyrene, such as SB (poly(styrene-b-butadiene)), SBS (poly(styrene-b-butadiene-b-styrene)), SIS (poly(styrene-b-isoprene-b-styrene)), SEBS (poly(styrene-b-ethylene / butylene-b-styrene)), poly(styrene-b-dimethylsiloxane-b-styrene), poly(α-methylstyrene-b-isoprene), poly(α-methylstyrene-b-isoprene-b-α-methylstyrene), poly(α-methylstyrene-b-propylene sulfide-b-α-methylstyrene), poly(α-methylstyrene-b-dimethylsiloxane-b-α-methylstyrene). Commercially available styrene block copolymers, such as the Kraton D and G series (from Kraton Polymer, Houston, Tex.), are particularly useful. Crystalline rubbers, such as poly(ethylene-co-propylene-co-5-methylene-2-norbornene) or EPDM (ethylene-propylene-diene terpolymer) rubbers, such as Vistalon 6505 (from Exxon Mobil, Houston, Tex.), and graft copolymers thereof have also been found to be very useful.

[0079] The thermoplastic elastomer can be dissolved in a solvent or solvent mixture that is immiscible with the carrier in the microcell and exhibits a specific gravity less than that of the carrier. Low surface tension solvents are preferably used in the outer coating composition due to their better wetting properties than the microcell walls and the fluid. Solvents or solvent mixtures having a surface tension of less than 35 dynes / cm are preferred. More preferably, a surface tension of less than 30 dynes / cm is preferred. Suitable solvents include alkanes (preferably C 6-12 Alkanes such as heptane, octane or Isopar solvents from Exxon Chemical Company, nonane, decane and their isomers), cycloalkanes (preferably C 6-12 Cycloalkanes such as cyclohexane and decalin), alkylbenzenes (preferably mono- or di-C 1-6 Alkylbenzenes, such as toluene, xylene, etc.), alkyl esters (preferably C 2-5 Alkyl esters such as ethyl acetate, isobutyl acetate, etc.) and C 3-5 Alkyl alcohols (such as isopropanol and the like and their isomers), alkylbenzenes and mixtures of alkanes are particularly useful.

[0080] In addition to polymer additives, the polymer mixture may also include a wetting agent (surfactant). Wetting agents, such as FC surfactants from 3M Company, Zonyl fluorosurfactants from DuPont, fluoroacrylates, fluoromethacrylates, fluorinated long chain alcohols, perfluorinated long chain carboxylic acids and their derivatives, and Silwet silicone surfactants from OSi, Greenwich, Conn, may also be included in the composition to improve the adhesion of the sealant to the microcells and provide a more flexible coating method. Other ingredients, including crosslinking agents (e.g., bisazides such as 4,4'-diazidediphenylmethane and 2,6-bis-(4'-azidobenzylidene)-4-methylcyclohexanone), vulcanizing agents (e.g., 2-benzothiazolyl disulfide and tetramethylthiuram disulfide), multifunctional monomers or oligomers (e.g., hexanediol, diacrylates, trimethylolpropane, triacrylates, divinylbenzene, diallylphthalene), thermal initiators (e.g., dilauroyl peroxide, benzoyl peroxide), and photoinitiators (e.g., isopropylthioxanthone (ITX), Irgacure 651 and Irgacure 369 from Ciba-Geigy) are also very useful for enhancing the physical-mechanical properties of the sealing film by crosslinking or polymerization during or after the overcoating process.

[0081] The microcell array 700 can be prepared by any of the above methods. Figures 7A-7D As shown in the cross-section in FIG. 1 , the microcell wall 102 extends upward from the backing layer 101 and the conductive layer 210 (first light-transmitting electrode layer 210) to form an open microcell. In one embodiment, the first light-transmitting electrode layer 210 is formed on or at the backing layer 101. Although Figures 7A-7D The first light-transmitting electrode layer 210 is shown to be continuous and extend over the backing layer 101, but the first light-transmitting electrode layer 210 may also be continuous and extend under or within the backing layer 101, or interrupted by the microcell walls 102. Prior to filling, the microcell array 700 may be cleaned and sterilized to ensure that the beneficial agents are not compromised prior to use.

[0082] The microcells are then filled with an electrophoretic medium 225 comprising charged particles in a non-polar fluid to form a plurality of filled microcells 770. Various techniques may be used to fill the microcells. In some embodiments, a doctor blade may be used to fill the microcells to the depth of the microcell walls 102. In other embodiments, inkjet microinjection may be used to fill the microcells. In other embodiments, a microneedle array may be used to fill the microcell array with the electrophoretic medium 225.

[0083] like Figure 7C As shown, after filling, the microcell is sealed by applying an aqueous sealing composition to form a sealed microcell 780 including a sealing film 230. In some embodiments, the sealing process may include exposure to heat, dry hot air, or ultraviolet radiation. The sealing film must have good barrier properties to the non-polar fluid of the electrophoretic medium 225.

[0084] In an alternative embodiment, each individual microcell can be filled with the desired mixture by using a repeated photolithography process. The method generally includes coating an empty microcell array with a positive working photoresist layer, selectively opening a certain number of microcells by imagewise exposure of the positive photoresist, then developing the photoresist, filling the opened microcells with the desired mixture, and sealing the filled microcells by a sealing process. These steps can be repeated to produce sealed microcells filled with other mixtures. The process can form a large sheet of microcells having a desired mixture ratio or concentration ratio.

[0085] The sealing of the filled microcell can be accomplished in a variety of ways. One method includes mixing an aqueous sealing composition with an electrophoretic medium composition. The aqueous sealing composition may be immiscible with the electrophoretic composition, preferably having a specific gravity lower than that of the electrophoretic medium composition. The two compositions, the sealing composition and the electrophoretic medium composition, are fully mixed and immediately applied to a plurality of microcells using a precision coating mechanical device, such as a Mayer rod, gravure printing, a scraper, a slot coating or a slit coating. Excess fluid is scraped off by a scraper or similar device. A small amount of weak solvent or solvent mixture, such as isopropanol, methanol or its aqueous solution can be used to clean the residual fluid on the top surface of the microcell partition wall. The aqueous sealing composition is then separated from the electrophoretic medium composition and floats on the top of the electrophoretic medium liquid composition. Alternatively, after the mixture of the electrophoretic medium composition and the aqueous sealing composition is filled into the microcell, a substrate can be laminated on the top to control the mixture metering of the composition and promote the phase separation of the aqueous sealing composition and the electrophoretic medium composition to form a uniform sealing film. The substrate used can be a functional substrate in the final structure, or can be a sacrificial substrate, such as a release substrate, which can be removed afterwards. The sealing film is then formed by hardening the aqueous sealing composition in situ (i.e. when in contact with the electrophoretic medium composition). The hardening of the aqueous sealing composition can be completed by ultraviolet or other forms of radiation, such as visible light, IR or electron beams. Alternatively, if a heat-curable or moisture-curable aqueous sealing composition is used, heat or moisture can also be used to harden the aqueous sealing composition.

[0086] In the second method, the electrophoretic medium composition can be first filled into the microcell, and the aqueous sealing composition is then coated on the filled microcell. The coating can be completed by conventional coating and printing methods, such as blanket coating, inkjet printing or other printing methods. In this method, the sealing film is formed in situ by hardening the aqueous sealing composition by solvent evaporation, radiation, heat, moisture or interfacial reaction. UV curing after interfacial polymerization is beneficial to the sealing process. A thin barrier layer is formed at the interface by interfacial polymerization, and the mixing between the electrophoretic medium composition and the sealing outer coating is significantly suppressed. Then the sealing is completed by a post-curing step, such as by ultraviolet radiation. The degree of mixing can be further reduced by using an aqueous sealing composition with a specific gravity lower than that of the electrophoretic medium composition. Volatile organic solvents can be used to adjust the viscosity and thickness of the sealing outer coating. The rheology of the aqueous sealing composition can be adjusted to obtain optimal sealability and coatability. When a volatile solvent is used in the outer coating, it is preferably immiscible with the solvent in the electrophoretic medium composition.

[0087] After filling and sealing the microcells, the sealed array can be laminated with a second electrode layer 250 comprising a plurality of electrodes. The second electrode layer 250 is attached to the sealing film 230 to form an electro-optical device 790, such as Fig.7D As shown. An adhesive can be used to attach the second electrode layer 250 to the sealing film 230 (the adhesive layer is not Fig.7D ). The adhesive can be conductive. The adhesive of the adhesive layer can be a pressure sensitive adhesive, a hot melt adhesive, or an adhesive that can be cured by heat, moisture, or radiation. If the top conductive layer is transparent to radiation, the laminating adhesive can be cured by radiation, such as ultraviolet light, through the top conductive layer. In other embodiments, multiple electrodes can be directly bonded to the array of sealed microcells.

[0088] In general, the microcells can be of any shape, and their size and shape can vary. In one system, the microcells can have a consistent size and shape. However, microcells with mixed shapes and sizes are possible. The openings of the microcells can be circular, square, rectangular, hexagonal, or any other shape. The size of the separation area between the openings can also vary. The size of each individual microcell can be between about 1×10 1 About 1×10 6 μm 2 , about 1×10 2 About 1×10 6 μm 2 , or about 1×10 3 About 1×10 5 μm 2 range.

[0089] The depth of the microcell can be from about 5 to about 200 μm, or from about 10 to about 100 μm. The ratio of the opening area of ​​the microcell to the total area of ​​the microcell layer is from about 0.05 to about 0.95, preferably from about 0.4 to about 0.9. The total area of ​​the microcell layer is the total area of ​​the side of the microcell layer on the same side as the microcell opening.

[0090] Electrophoretic displays typically include an electrophoretic material layer and at least two other layers disposed on opposite sides of the electrophoretic material, one of the two layers being an electrode layer. In most such displays, both layers are electrode layers, and one or both of the electrode layers are patterned to define the pixels of the display. For example, one electrode layer may be patterned as an elongated row electrode and the other electrode layer may be patterned as an elongated column electrode extending at right angles to the row electrode, with the pixel being defined by the intersection of the row electrode and the column electrode. Alternatively and more commonly, one electrode layer has the form of a single continuous electrode and the other electrode layer is patterned as a matrix of pixel electrodes, each of which defines a pixel of the display. In another type of electrophoretic display intended for use with a stylus, print head or similar movable electrode separated from the display, only one of the layers adjacent to the electro-optical material layer includes an electrode, and the layer on the opposite side of the electro-optical material layer is generally a protective layer intended to prevent the movable electrode from damaging the electro-optical material layer.

[0091] The manufacture of three-layer electro-optical displays typically involves at least one lamination operation. For example, in several of the above-mentioned MIT and E Ink patents and applications, there is a description of a method for manufacturing an encapsulated electrophoretic display, in which an encapsulated electrophoretic medium containing capsules in a binder is applied to a flexible substrate containing indium tin oxide (ITO) or a similar conductive coating on a plastic film. A backplane is prepared separately, the backplane containing an array of pixel electrodes and an appropriate conductor arrangement to connect the pixel electrodes to a drive circuit. To form the final display, the substrate with the electro-optical material layer is laminated to the backplane using a laminating adhesive.

[0092] The aforementioned U.S. Patent No. 6,982,178 describes a method of assembling a solid electro-optic device that is well suited for mass production. Basically, the patent describes a so-called "front plane laminate" ("FPL") that includes, in order, a light-transmitting electrode layer; a layer of electro-optic material in electrical contact with the light-transmitting electrode layer; an adhesive layer; and a release sheet. An example of this structure is shown in FIG. Figure 3 Available in Figure 3In the present invention, the electrophoretic material layer includes a microcell layer and a sealing film. Generally, the light-transmitting electrode layer will be carried on a light-transmitting substrate, which is preferably flexible in the sense that the substrate can be manually wrapped around a roller having a diameter of (supposedly) 10 inches (254 mm) without permanent deformation. The term "light-transmitting" is used in this patent and herein to refer to a layer so designated that transmits sufficient light to enable an observer viewing through the layer to observe a change in the display state of the electrophoretic medium, which will generally be viewed through the light-transmitting electrode layer and the adjacent substrate (if present); in the case where the electrophoretic medium displays a change in reflectivity at non-visible wavelengths, the term "light-transmitting" should of course be interpreted as referring to the transmission of the relevant non-visible wavelengths. The substrate will generally be a polymer film and will generally have a thickness in the range of about 1 to about 25 mils (25 to 634 μm), preferably about 2 to about 10 mils (51 to 254 μm). The light-transmitting electrode layer is conveniently a thin metal or metal oxide layer, such as an aluminum layer or an ITO layer, or can be a conductive polymer. Poly(ethylene terephthalate) (PET) films coated with aluminum or ITO are commercially available, for example, from EI duPont de Nemours & Company, Wilmington DE as "aluminized Mylar" ("Mylar" is a registered trademark), and such commercial materials can be used in front plane laminates with good results. Assembly of an electrophoretic display using such front plane laminates can be accomplished by removing a release sheet from the front plane laminate and contacting the adhesive layer with the backplane under conditions effective to cause the adhesive layer to adhere to the backplane, thereby securing the adhesive layer, electro-optical material layer, and light-transmitting electrode layer to the backplane. This method is well suited for mass production because the front plane laminates can be mass produced, typically using roll-to-roll coating techniques, and then cut into sheets of any size required for use with a particular backplane.

[0093] U.S. Patent No. 7,561,324 describes a so-called "double release sheet" which is essentially a simplified version of the front plane laminate of the aforementioned U.S. Patent No. 6,982,178. One form of double release sheet includes a layer of electro-optical material sandwiched between two adhesive layers, one or both of which are covered by a release sheet. Figure 4 An example of a double release sheet of this form is shown. Figure 4In the embodiment of the present invention, the electrophoretic material layer includes a microcell layer and a sealing film. Another form of a double release sheet includes a solid electro-optical material layer sandwiched between two release sheets. Both forms of double release films are intended for use in a process that is generally similar to that used to assemble an electrophoretic display from a front plane laminate already described, but involves two separate lamination processes; generally, in a first lamination, the double release sheet is laminated to a front electrode layer (first light-transmitting electrode layer) to form a front subassembly, and then in a second lamination, the front subassembly is laminated to a backplane to form the final display, but if desired, the order of the two laminations can be reversed. The backplane includes a second electrode layer.

[0094] U.S. Patent No. 7,839,564 describes a so-called "inverted front plane laminate", which is a variation of the front plane laminate described in the above-mentioned U.S. Patent No. 6,982,178. The inverted front plane laminate may include, in sequence: at least one of a light-transmitting protective layer and a light-transmitting electrode layer; an adhesive layer; an electro-optical material layer; and a release sheet. The inverted front plane laminate is used to form an electro-optical device having a laminated adhesive layer between the electro-optical material layer and the light-transmitting electrode layer; a second, generally thin adhesive layer may or may not be present between the electro-optical material layer and the backplane. Such an electro-optical device can combine good resolution with good low temperature performance.

[0095] Electrophoresis medium

[0096] In the context of the present invention, electrophoretic medium refers to the composition in the microcell. For display applications, the microcell can be filled with at least one type of charged pigment particles in a non-polar fluid. The electrophoretic medium can contain one type of charged particles or more than one type of particles with different colors, charges and charge polarities. Under the influence of the electric field applied across the electro-optical material layer, the charged particles move through the electrophoretic medium. The charged particles can be inorganic or organic pigments, which have a polymer surface treatment to improve their stability. The electrophoretic medium can contain pigments with white, black, cyan, magenta, yellow, blue, green, red and other colors. The electrophoretic medium can also contain charge control agents, charge adjuvants, rheology modifiers and other additives. Examples of nonpolar fluids include hydrocarbons such as Isopar, decaline (DECALIN), 5-ethylidene-2-norbornene, fatty oils, paraffin oils, silicone fluids, aromatic hydrocarbons such as toluene, xylene, phenylxylylethane, dodecylbenzene or alkylnaphthalene, halogenated solvents such as perfluorodecalin, perfluorotoluene, perfluoroxylene, dichlorobenzotrifluoride, 3,4,5-trichlorobenzotrifluoride, chloropentafluorobenzene, dichlorononane or pentachlorobenzene, and perfluorinated solvents such as FC-43, FC-70 or FC-5060 from 3M Company, St. Paul MN, low molecular weight halogen-containing polymers such as poly(perfluoropropylene oxide) from TCI America, Portland, Oregon, poly(chlorotrifluoroethylene) such as Halocarbon Oils from Halocarbon Product Corp., River Edge, NJ, perfluoropolyalkyl ethers such as Galden from Ausimont or Krytox Oils and Greases from DuPont, Delaware K-Fluid Series, polydimethylsiloxane-based silicone oil (DC-200) from Dow-corning.

[0097] The electrophoretic medium may contain two types of charged particles with different colors, the first type of charged particles having a first charge polarity and the second type of charged particles having a second charge polarity opposite to the first charge polarity. The first type of charged particles may be black and the second type of charged particles may be white.

[0098] The electrophoretic medium may contain three types of charged particles each having a different color, the first type of charged particles having a first charge polarity, the second type of charged particles having a second charge polarity opposite to the first charge polarity, and the third type of charged particles having a third charge polarity that is the same as the first or second charge polarity. The first type of charged particles may be black, the second type of charged particles may be white, and the third type of charged particles may be selected from red, yellow, blue, cyan, magenta, green, and orange.

[0099] The electrophoretic medium may include four types of charged particles each having a different color, the first type of charged particles having a first charge polarity, the second type of charged particles having a first charge polarity, the third type of charged particles having a second charge polarity opposite to the first charge polarity, and the fourth type of charged particles having a second charge polarity. The charge amount of the first type of particles may be higher than the charge amount of the second type of particles, and the charge amount of the third type of particles may be higher than the charge amount of the fourth type of particles. In one example, the first type of charged particles are cyan, the second type of charged particles are magenta, the third type of particles are yellow, and the fourth type of charged particles are white.

[0100] The electrophoretic medium may include four types of charged particles each having a different color, the first type of charged particles having a first charge polarity, the second type of charged particles having a first charge polarity, the third type of charged particles having a first charge polarity, and the fourth type of charged particles having a second charge polarity opposite to the first charge polarity. The charge amounts of the first, second, and third particles may be different from each other. The charge amount of the third type of particles may be higher than the charge amount of the first type of particles, and the charge amount of the first type of particles may be higher than the charge amount of the second type of particles. In one example, the first type of particles are cyan, the second type of particles are magenta, the third type of particles are yellow, and the fourth type of particles are white.

[0101] The electrophoretic medium may include five types of charged particles each having a different color, the first type of charged particles having a first charge polarity, the second type of charged particles having a first charge polarity, the third type of particles having a first charge polarity, the fourth type of particles having a second charge polarity opposite to the first charge polarity, and the fifth type of particles having a second charge polarity. The amounts of the first, second, and third charges may be different from each other. The amount of charge of the third type of particles may be higher than the amount of charge of the first type of particles, and the amount of charge of the first type of particles may be higher than the amount of charge of the second type of particles. The charge of the fourth type of particles may be higher than the charge of the fifth type of charged particles. In one example, the first type of particles are cyan, the second type of particles are magenta, the third type of particles are black, the fourth type of particles are yellow, and the fifth type of particles are white.

[0102] Sealing films from aqueous sealing compositions

[0103] The sealing film plays an important role in the performance of the microcell electro-optical device. The sealing film can be formed by coating a sealing composition on the microcell layer of the electro-optical device. Because the sealing film contacts the electrophoretic medium and seals the electrophoretic medium in the microcell, it must be virtually insoluble in the non-polar fluid of the electrophoretic medium, and it must be a good barrier to the non-polar fluid so that the non-polar fluid does not diffuse out of the microcell during the life of the device. The poor barrier properties of the sealing film to the non-polar fluid of the electrophoretic medium lead to a reduction in fluid from the electrophoretic medium and sagging of the sealing film. In addition, the sealing film must not absorb a significant amount of moisture from the environment. That is, it must prevent environmental moisture from entering the electrophoretic medium of the device. This moisture affects the conductivity of the sealing film and the electrophoretic medium, and has a negative impact on the electro-optical performance of the device. The sealing film that seals the microcell layer must not have significant coating defects. Such defects have a negative impact on the electro-optical performance of the device. During the service life of the device, the sealing film must have mechanical elasticity. It should also have an optimal volume resistivity that is virtually constant over time.

[0104] Another important property of the sealing film is its volume resistivity. If the resistivity of the sealing film is too high, a significant voltage drop will occur within the sealing film, requiring an increase in the voltage across the electrodes to operate the device. Increasing the voltage across the electrodes in this way is undesirable because it increases the power consumption of the display and may require the use of more complex and expensive control circuits to handle the increased voltage. On the other hand, if the volume resistivity of the sealing film is too low, undesirable crosstalk between adjacent pixel electrodes is observed, reducing image quality. In addition, because volume resistivity generally increases rapidly as temperature decreases, an excessively high volume resistivity of the sealing film has a negative impact on the low temperature electro-optical performance of the display. The sealing film may have a volume resistivity of 10 8 The sealing film may have a volume resistivity of 1.0×10 7 to 1.0×10 12 Ohm·cm, 1.0×10 7 to 1.0×10 11 Ohm·cm, 1.0×10 8 to 1.0×10 11 , 3.5×10 7 Up to ×10 12 Ohm cm or 1.0×10 8 to 1.0×10 10 The sealing film may have a volume resistivity of 10 ohm cm. 11 Ohm cm or less, or 10 10 Volume resistivity of ohm-cm or less.

[0105] The sealing film can be prepared from an aqueous sealing composition. The aqueous sealing composition comprises 15 to 60 wt % of a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, based on the weight of the aqueous sealing composition excluding water, 7 to 29 wt % of a polyurethane, based on the weight of the aqueous sealing composition excluding water, and 0.05 to 10 wt % of a rheology modifier, based on the weight of the aqueous sealing composition excluding water. The rheology modifier can be a hydrophobically modified ethoxylated urethane or an alkali swellable emulsion polymer, or a combination thereof.

[0106] The rheology modifier may be present in the aqueous sealing composition in an amount of 0.05 to 10 wt %, 0.05 to 3 wt %, 0.05 to 2 wt %, 0.07 to 1 wt % or 0.08 to 1 wt % of the weight of the aqueous sealing composition excluding water. The rheology modifier increases the stability of the aqueous sealing composition during its storage. It also facilitates film formation, improves seal stability, and reduces defects in the sealing film. Examples include associative thickeners, alkali swellable acrylic emulsion polymers, and other polymeric thickeners. The aqueous sealing composition may be shear thinning, that is, its viscosity decreases at higher shear rates. For example, the rheological curve of the aqueous sealing composition may show a shear-thinning viscosity at 10 -4 The viscosity at a shear rate of l / s and 10 2 The viscosity decreases by a factor of 5 to 10,000 at a shear rate of 1 / s.

[0107] Hydrophobically modified ethoxylated urethanes (or HEURs) are rheology modifiers that may contain polyethylene glycol blocks covalently linked via urethane. They belong to the family of "associative thickeners". Associative thickeners have both hydrophilic and hydrophobic regions. Examples of HEUR rheology modifiers are polyethylene oxide blocks linked via urethane and modified with nonylphenol hydrophobic groups. The polyethylene oxide blocks of HEUR rheology modifiers have relatively low molecular weights, e.g., less than 12,000 Daltons (g / mol), typically 50-700 Daltons. HEUR rheology modifiers are nonionic polymers that are generally soluble in water at any pH. The water solubility of HEUR rheology modifiers is a result of the presence of ethylene oxide groups in their molecular structure. HEURs may be branched or unbranched polymers. They may have terminal long-chain alkyl or alkylene groups containing 8 to 30 carbon atoms. Typical alkyl groups are, for example, dodecyl or stearyl groups; typical alkenyl groups are, for example, oleyl groups; typical aryl groups are phenyl groups; typical alkylated aryl groups are, for example, nonylphenyl groups. Some HEUR moles also contain one or more internal hydrophobic blocks or groups.

[0108] Non-limiting examples of HEUR rheology modifiers include ACULYN supplied by Dow Chemical. TM44. ACULYN TM 46. ​​ACUSOL TM 880、ACUSOL TM 882, ACRYSOL TM RM-3000, ACRYSOL TM RM-895, ACRYSOL TM RM-8W、ACRYSOL TM RM-12W、ACRYSOL TM RM-995, ACRYSOL TM SCT-275, ACRYSOL TM RM-845, ACRYSOL TM RM-825, ACRYSOL TM RM-6000, ACRYSOL TM RM-5000, ACRYSOL TM RM 2020E、ACRYSOL TM RM-8W、ACRYSOL TM RM-725, supplied by BASF PU 1190, PU 1191, PU 1291, PU 1241 and PU 1331, supplied by Elementis Specialties 212. 255, 655, 278, 678, 288, 299 and 475, provided by BYK T 1000, L 1400, M 2600VF, H 7500VF, 3300, TEGO provided by TEGO series, and provided by Munzing PUR 61, PUR 50 and PUR85.

[0109] Alkali swellable emulsion (ASE) rheology modifiers are polymers produced using emulsion polymerization. In contrast to HEUR rheology modifiers, ASE rheology modifiers are not associative thickeners. They can be formed from hydrophilic monomers such as (meth)acrylic acid monomers and less hydrophilic monomers such as (meth)acrylate monomers of lower alcohols ((meth)acrylate monomers of C1 to C4 fatty alcohols, such as, for example, ethyl acrylate, propyl acrylate, butyl acrylate, and methyl methacrylate). ASE rheology modifiers can provide thickening effects to aqueous compositions at high pH. At high pH values, the (meth)acrylic acid group is soluble in water, while the (meth)acrylate ester is not soluble in water. At low pH values, the polymer is not soluble in water and does not thicken the aqueous composition. At high pH values, the acid is neutralized to its salt and the polymer swells, resulting in a thicker composition. Typically, ASE rheology modifiers have a relatively high weight average molecular weight, i.e., greater than 300,000 Daltons (g / mol), greater than 400,000 Daltons, or greater than 500,000 Daltons. Examples of hydrophilic groups include acrylic acid, methacrylic acid, and maleic acid. Examples of hydrophobic groups include acrylates and methacrylates of fatty alcohols. Non-limiting examples of ASE rheology modifiers include ASE® supplied by BASF 1125, 1130, ACULYN TM 33. ACULYN TM 38. ACUSOL TM 810A、ACUSOL TM 830、ACUSOL TM 835、ACUSOL TM 842 and ACRYSOL TM RM-38 (supplied by Dow Chemical), and Aqua 30 (supplied by Lubrizol Corporation).

[0110] Hydrophobically modified alkali swellable emulsion polymer (HASE) rheology modifiers are non-preferred rheology modifiers for the aqueous sealing compositions of the present invention. These rheology modifiers swell and thicken aqueous compositions at high pH values. They include monomers with high hydrophobicity. For example, ASE polymers can be formed from monomers such as (meth)acrylic acid monomers and (meth)acrylic esters of C1-C4 alcohols, and HASE polymers can be formed from monomers such as (meth)acrylic acid monomers and C8-C 22 (Meth)acrylic acid esters of alcohols are formed.

[0111] Non-limiting examples of HASE rheology modifiers include HASE, supplied by BASF PU 1212、1125、 1130, ACULYN supplied by Dow Chemical TM Excel, ACRYSOL TM TT615、ACULYN TM 22. ACULYN TM 88. ACUSOL TM 801S、ACUSOL TM 805S、ACUSOL TM 820 and ACUSOL TM 823.

[0112] The aqueous sealing composition may further include a conductive filler. The content of the conductive filler in the aqueous sealing composition may be 5 to 70 weight % of the weight of the aqueous sealing composition excluding water. The filler of the aqueous sealing composition may be selected from carbon black, graphene, graphite and carbon nanotubes. The filler reduces the volume resistivity of the sealing film, but it may also affect other properties of the layer, such as its surface energy. In order to be effective as a filler, carbon black must have good dispersibility in the aqueous sealing composition. The content of the conductive carbon black in the aqueous sealing composition may be 10 to 60 weight %, 15 to 50 weight %, 20 to 45 weight % or 30 to 40 weight % of the aqueous sealing composition.

[0113] The oil absorption value of the carbon black used in the aqueous sealing composition may be 100 cm per 100 mg of carbon black. 3 or less. Carbon black manufacturers generally report the oil absorption value as OAN (oil absorption number), measured using a method according to ASTM 2414. It represents the structure and degree of aggregation of the carbon black particles. That is, the larger the OAN, the higher the structure of the carbon black particles (connected to each other and having a branched structure) and / or the higher the degree of aggregation of the particles. More structured / aggregated carbon blacks generally provide higher conductivity for the sealing film, although the conductivity may also depend on the dispersibility of the filler, and a higher OAN indicates that it may be more difficult to disperse the carbon black. The carbon black filler of the aqueous sealing composition may preferably have an average primary particle diameter greater than 30nm. This is another physical property of the carbon black grade that may be reported by the carbon black manufacturer. The primary particles can be determined by electron microscopy. Generally, carbon black with a very small average primary particle diameter is difficult to disperse. The total surface area of ​​the carbon black may be less than 80m 2 / g, less than 75m 2 / g or less than 70m 2 / g. This is another common physical property often reported by carbon black manufacturers. It is measured using nitrogen adsorption according to ASTM D 6556. Carbon black can have a volume resistivity higher than 0.1 ohm cm, which is measured in powder form using the ASTM D 2663 method at a pressure of 40 MPa.

[0114] The total surface energy of the conductive carbon black of the aqueous sealing composition may be higher than 40 mN / m, or higher than 55 mN / m, measured by the Washburn method using hexane as the test liquid. The total surface energy of the conductive carbon black of the aqueous sealing composition may be from 40 mN / m to 80 mN / m, from 40 mN / m to 70 mN / m, or from 40 mN / m to 65 mN / m. The dispersion component of the surface energy of the conductive carbon black may be higher than 15 mN / m, measured by the Washburn method using hexane as the test liquid. The dispersion component of the conductive filler may be from 15 mN / m to 40 mN / m, or from 15 mN / m to 30 mN / m.

[0115] The content of the water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in the aqueous sealing composition can be 15 to 60 weight %, 18 to 55 weight %, 20 to 50 weight % or 22 to 40 weight % of the weight of the aqueous sealing composition excluding water.

[0116] The degree of hydrolysis of poly(vinyl alcohol) homopolymers is 90% to 99.5%, and the degree of hydrolysis of poly(vinyl alcohol-co-ethylene) copolymers is 90% to 99.5%, and the ethylene content is less than 10%. The degree of hydrolysis of poly(vinyl alcohol) homopolymers and poly(vinyl alcohol-co-ethylene) copolymers can be 92% to 99%, or 92% to 95%. The ethylene content of poly(vinyl alcohol-co-ethylene) copolymers can be less than 9%, less than 8.5%, or less than 8%. The degree of hydrolysis of poly(vinyl alcohol) homopolymers and copolymers is usually reported by the manufacturer of such polymers, which represents the ratio of vinyl alcohol units (in moles) to the total ethylene units in the polymer. The other units are generally vinyl acetate. The manufacturer also reports the ethylene content of poly(vinyl alcohol-co-ethylene) copolymers, which represents the ratio of ethylene units (in moles) to the other units in the polymer. In this case, the other units are vinyl alcohol and vinyl acetate. The poly(vinyl alcohol) homopolymer and poly(vinyl alcohol-co-ethylene) copolymer of the aqueous sealing composition may have a weight average molecular weight (MW) of 1,000 to 1,000,000 Daltons (g / mole), or 10,000 to 500,000 Daltons, or 20,000 to 400,000 Daltons.

[0117] Polyurethane is generally prepared by a polyaddition method involving diisocyanates. Non-limiting examples of polyurethane include polyether polyurethane, polyester polyurethane, polycarbonate polyurethane, polyether polyurea, polyurea, polyester polyurea, polyester polyurea, polyisocyanate (e.g., polyurethane comprising isocyanate bonds) and polycarbodiimide (e.g., polyurethane comprising carbodiimide bonds). Typically, polyurethane contains urethane groups. The polyurethane used in the aqueous sealing composition and sealing film described herein can be prepared using methods known in the art. The polyurethane of the aqueous sealing composition of the present invention is polyester polyurethane, polycarbonate polyurethane and mixtures thereof. The polyurethane of the aqueous sealing composition can have a weight average molecular weight (MW) of 1000 to 2000000 Dalton (g / mol), or 10000 to 300000 Dalton, or 15000 to 200000 Dalton. Polyurethane can be added to the aqueous sealing composition in the form of an aqueous solution, an aqueous dispersion, or an aqueous emulsion or latex.

[0118] The content of the polyurethane in the aqueous sealing composition may be 7 to 29 wt %, 8 to 25 wt %, 12 to 22 wt %, or 14 to 20 wt % based on the weight of the aqueous sealing composition excluding water.

[0119] The aqueous sealing composition may include a polyurethane crosslinker (or otherwise referred to as a polyurethane crosslinker). The content of the polyurethane crosslinker in the aqueous sealing composition may be 0.1 to 8% by weight of the polyurethane crosslinker of the aqueous sealing composition excluding water. In the process of curing the aqueous sealing composition to prepare a sealing film, the polyurethane crosslinker forms a chemical bond between the polyurethanes of the aqueous sealing composition, and may form a chemical bond with the polymer molecules of the microunits, increasing the adhesion between the sealing film and the microunits. The polyurethane crosslinker is preferably soluble or dispersed in an aqueous carrier of the aqueous sealing composition. The crosslinker may be a monomer, an oligomer or a polymer. Examples of polyurethane crosslinkers include polyisocyanates, polyfunctional polycarbodiimides, polyfunctional aziridines, silane coupling agents, boron / titanium / zirconium-based crosslinkers or melamine formaldehyde. The polycarbodiimide crosslinker is reactive under acidic pH conditions. Preferably, the polyurethane crosslinker does not contain a sulfosuccinate surfactant. The content of the polyurethane crosslinking agent in the aqueous sealing composition may be 0.2 to 6 wt %, 0.4 to 4 wt %, 0.5 to 3 wt %, 0.6 to 2 wt % or 0.7 to 1.8 wt % of the weight of the aqueous sealing composition excluding water.

[0120] The inventors of the present invention have found that an aqueous sealing composition comprising a combination of a water-soluble poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer and a polyurethane can form a sealing film with excellent properties, wherein the interfacial tension between the water-soluble poly(vinyl alcohol) polymer or the poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane is less than 2 mN / m.

[0121] Extensive experimental work has also revealed that excellent performance is also observed from aqueous sealing compositions comprising a combination of a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and a polyurethane wherein the polar component of the polyurethane surface energy is 10 to 20 mN / m.

[0122] The aqueous sealing composition may further comprise 1 to 40 wt % of a water-soluble ether, based on the weight of the aqueous sealing composition excluding water. The aqueous sealing composition may comprise 1 to 30 wt %, 1 to 25 wt %, 1 to 22 wt %, 1 to 20 wt %, 1 to 15 wt %, 1 to 10 wt %, 1 to 5 wt % or 1 to 3 wt % of a water-soluble ether, based on the weight of the aqueous sealing composition excluding water. The content of water-soluble ether in the aqueous sealing composition may be higher than 0.2% by weight of the aqueous sealing composition excluding water, higher than 0.5% by weight of the aqueous sealing composition excluding water, higher than 1% by weight of the aqueous sealing composition excluding water, higher than 2% by weight of the aqueous sealing composition excluding water, higher than 5% by weight of the aqueous sealing composition excluding water, higher than 6% by weight of the aqueous sealing composition excluding water, higher than 7% by weight of the aqueous sealing composition excluding water, higher than 8% by weight of the aqueous sealing composition excluding water or higher than 10% by weight of the aqueous sealing composition excluding water. The content of the water-soluble ether in the aqueous sealing composition may be less than 40 wt % of the weight of the aqueous sealing composition excluding water, less than 30 wt % of the weight of the aqueous sealing composition excluding water, less than 20 wt % of the weight of the aqueous sealing composition excluding water, less than 15 wt % of the weight of the aqueous sealing composition excluding water, less than 10 wt % of the weight of the aqueous sealing composition excluding water, less than 5 wt % of the weight of the aqueous sealing composition excluding water or less than 2 wt % of the weight of the aqueous sealing composition excluding water.

[0123] The water-soluble ether has a weight average molecular weight of 75 to 5000 Daltons (g / mol). The water-soluble ether may have a weight average molecular weight of 85 to 3000 Daltons, 90 to 1000 Daltons, 90 to 500 Daltons, or 90 to 300 Daltons. The water-soluble ether may have a weight average molecular weight greater than 75, greater than 90, greater than 100, or greater than 200. The water-soluble ether may have a weight average molecular weight less than 5000, less than 3000, less than 1000, less than 500, less than 300, less than 200, or less than 150.

[0124] The water-soluble ether is a polar compound soluble in water and a polar organic solvent. The water-soluble ether can be represented by Formula II, Formula III or Formula IV.

[0125]

[0126] The value of n is 1 to 145. The value of n can be 1 to 100, 1 to 50, 1 to 20, 1 to 10, 1 to 5, 1 to 4, 1 to 3 or 1 to 2. R1 is hydrogen, a methyl or ethyl group; R2, R3, R4, R5, R6 and R7 are independently selected from hydrogen, a straight or branched alkyl group containing 1 to 6 carbon atoms, a phenyl and a benzyl group. Formula II contains at least one ether functional group. Formula III contains at least one ether functional group. Formula IV contains at least one ether functional group.

[0127] The water-soluble ether may be selected from ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol n-butyl ether, ethylene glycol monoisobutyl ether, ethylene glycol monotert-butyl ether, ethylene glycol monobenzyl ether, ethylene glycol monophenyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-propyl ether, ethylene glycol diisopropyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol monoisopropyl ether, diethylene glycol n-butyl ether, diethylene glycol Monoisobutyl ether, diethylene glycol monotert-butyl ether, diethylene glycol monobenzyl ether, diethylene glycol monophenyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol di-n-propyl ether, diethylene glycol diisopropyl ether, diethylene glycol di-n-butyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol mono-n-propyl ether, triethylene glycol monoisopropyl ether, triethylene glycol monobutyl ether, triethylene glycol monoisobutyl ether, triethylene glycol monotert-butyl ether, triethylene glycol monobenzyl ether, Triethylene glycol monophenyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol di-n-propyl ether, triethylene glycol diisopropyl ether, tetraethylene glycol monomethyl ether, tetraethylene glycol monoethyl ether, triethylene glycol monophenyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol monomethyl ether, polyethylene glycol monoethyl ether, polyethylene glycol monophenyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol monoisopropyl ether, propylene glycol mono-n-butyl ether, propylene glycol monoisobutyl ether, propylene glycol monophenyl ether, propylene glycol Dimethyl ether, propylene glycol diethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol monoisopropyl ether, dipropylene glycol mono-n-butyl ether, dipropylene glycol monoisobutyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol di-n-propyl ether, dipropylene glycol diisopropyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol monoisopropyl ether, tripropylene glycol mono-n-butyl ether, tripropylene glycol monoisobutyl ether or a mixture thereof.

[0128] The aqueous sealing composition can also include a wetting agent, also referred to as a surfactant. Non-limiting examples of wetting agents include FC surfactants from 3M, Zonyl fluorinated surfactants from DuPont, fluoroacrylates, fluoromethacrylates, fluorinated long-chain alcohols, perfluorinated long-chain carboxylic acids and their derivatives, and Silwet silicone surfactants from OSi, Greenwich, Conn. The wetting agent can increase the affinity between the sealing film and the microunit, increase the interfacial area between them, and improve the adhesion of the sealing film to the microunit, providing a more flexible coating process. The content of the surfactant in the aqueous sealing composition can be 0.001 to 5 weight %, 0.01 to 5 weight % or 0.01 to 2 weight % of the weight of the aqueous sealing composition excluding water.

[0129] The aqueous sealing composition may include water in an amount of 20 to 95 wt %, 50 to 94 wt %, 70 to 92 wt %, 75 to 90 wt %, or 80 to 88 wt % based on the weight of the aqueous sealing composition.

[0130] The aqueous sealing composition may also include a pH adjuster. The pH adjuster is added to the aqueous sealing composition to adjust its pH to a value of 6.5 to 8.5. An example of a pH adjuster is ammonium hydroxide, but various acids and bases may be used. The pH adjuster increases the pH of the aqueous sealing composition, which may reduce the crosslinking rate of the aqueous sealing composition before its use, and provides optimal pH conditions for the interaction of the rheology modifier with the particles of the aqueous sealing composition, improving its efficacy. The pH adjuster may be used in an amount of 0.2% to 1% by weight of the weight of the aqueous sealing composition excluding water.

[0131] The aqueous sealing composition can be used to form a sealing film by applying the aqueous sealing composition and drying or curing the aqueous sealing composition. The sealing film may include most of the ingredients of the aqueous sealing composition. If the aqueous composition includes a polyurethane crosslinker, the polyurethane crosslinker is incorporated into the polyurethane polymer of the sealing film during the curing process. In addition, during the drying or curing of the aqueous sealing composition to prepare the sealing film, the water of the sealing composition is evaporated. If the aqueous sealing composition includes a water-soluble ether, the formed sealing film also includes the water-soluble ether of the aqueous sealing composition, although some of the water-soluble ether evaporates during the formation of the sealing film. Unless otherwise stated, if there is any residual or absorbed water or moisture or water-soluble ether in the sealing film, the disclosed content of the components of the sealing film is calculated by weight % of the component excluding residual water, residual water-soluble ether and absorbed water.

[0132] The sealing film comprises 15 to 60 wt % of a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, 7 to 29 wt % of a polyurethane, and 0.05 to 10 wt % of a rheology modifier, based on the weight of the sealing film. The poly(vinyl alcohol) homopolymer has a degree of hydrolysis of 90 to 99.5%. The poly(vinyl alcohol-co-ethylene) copolymer has a degree of hydrolysis of 90 to 99.5% and an ethylene content of less than 10%. The rheology modifier is a hydrophobically modified ethoxylated urethane (HEUR) or an alkali swellable emulsion polymer (ASE). The sealing film may further comprise a conductive filler. The conductive filler may be carbon black. The sealing film may comprise 11 to 60 wt %, 24 to 55 wt %, 29 to 50 wt %, or 30 to 45 wt % of conductive carbon black, based on the weight of the sealing film.

[0133] The sealing film may contain a surfactant (wetting agent). The content of the surfactant in the sealing film may be 0.001 to 5 wt %, 0.01 to 5 wt % or 0.01 to 2 wt % of the weight of the aqueous sealing composition. The surfactant may be an anionic, cationic, zwitterionic or nonionic surfactant. The surfactant may be a fluorinated surfactant. The surfactant may be a siloxane surfactant containing a polydimethylsiloxane group in its molecular structure.

[0134] The sealing film may contain 4.5 to 25 wt% of the water-soluble ether by weight of the sealing film. The sealing film may contain 4.5 to 10 wt%, or 5 to 9 wt%, 5 to 8 wt%, or 5 to 7 wt% of the water-soluble ether by weight of the sealing film. The content of water-soluble ether in the sealing film may be higher than 4.5 wt%, higher than 5 wt%, higher than 6 wt%, higher than 7 wt%, higher than 8 wt%, higher than 9 wt%, or higher than 10 wt% of the weight of the sealing film. The content of water-soluble ether in the sealing film may be lower than 25 wt%, lower than 20 wt%, lower than 15 wt%, lower than 10 wt%, or lower than 5 wt% of the weight of the sealing film.

[0135] It is believed that the addition of water-soluble ethers to the aqueous sealing composition and the sealing film reduces the resistance of the interface between the sealing film and one or two adjacent layers, such as the sealing film-adhesive interface and the sealing film-electrophoretic medium interface. As shown in the Examples section, this reduction in interfacial resistance has been experimentally demonstrated by volume resistivity measurements and electrical impedance spectroscopy experiments. Importantly, this resistance of the interface does not affect the conductivity of the sealing film itself. In fact, as shown in the data, the sealing film of the present invention has a higher volume resistivity than the control film that does not contain the water-soluble ether. As described above, the higher volume resistivity of the sealing film helps to reduce frosting, which is a well-known phenomenon in the field of electro-optics.

[0136] The sealing film prepared from the aqueous sealing composition can be used to seal the microcell of the electro-optical device. The electro-optical device includes a conductive layer; a microcell layer including a plurality of microcells, each microcell including an opening, each microcell containing an electrophoretic medium, the electrophoretic medium containing charged particles in a non-polar carrier; a sealing film, the sealing film spanning the opening of each microcell; an adhesive layer; and an electrode layer.

[0137] Generally, the sealing film of electro-optical device plays an important role in display performance. The poor barrier properties of the sealing film cause the non-polar fluid of the electrophoretic medium to escape from the electro-optic material layer over time, which causes the electro-optical performance of the display to deteriorate severely. It is observed that the content of poly (vinyl alcohol) homopolymer or poly (vinyl alcohol-co-ethylene) copolymer that increases the sealing film improves its barrier properties. However, the sealing film with high content of poly (vinyl alcohol) homopolymer or poly (vinyl alcohol-co-ethylene) copolymer increases its hygroscopicity, which is also undesirable.

[0138] The inventors of the present invention have surprisingly found that aqueous compositions comprising rheology modifiers selected from HEUR and ASE improve the coating quality of sealing films. That is, they reduce coating defects. If defects are present, the electro-optical performance of the corresponding device is poor. Coating defects may be associated with dewetting, stratification, chattering or turbid spot unevenness (CSM). These effects will be described in detail below. Specifically, when (a) the viscosity ratio is less than 7, the viscosity ratio is 1 to 7, 2 to 7 or 0.5 to 7, (b) the HB rate index is 0.7 or higher, 0.7 to 1, 0.7 to 0.9 or 0.7 to 2, and (c) the thixotropic index is 1.5 or higher, or 1.5 to 3, reduced defects (higher coating quality) of the sealing film are observed.

[0139] As described in the Examples section, the viscosity ratio of the aqueous sealing composition is determined by the ratio of the viscosity at a low shear rate divided by the viscosity at a high shear rate. The HB rate index of the aqueous sealing composition is determined by measuring the viscosity of the composition via a shear rate ramp, constructing a stress to shear rate graph and analyzing the graph based on the Herschel-Bulkley model, as described in the Examples section. The thixotropic index is the viscosity ratio measured by a thixotropic ring experiment, in which a low to high shear rate is applied to the aqueous composition, followed by a high to low shear rate. The thixotropic index represents the thixotropic behavior of the aqueous sealing composition. The inventors have conducted a detailed study of the rheological properties of various aqueous sealing compositions, then used the aqueous composition to form a device with a corresponding film, and determined the coating quality and performance of this sealing film. Surprisingly, it was found that an aqueous composition comprising HEUR and ASE rheology modifiers provides a sealing film showing better performance and significantly lower defects. It was also observed that the use of fluorosurfactants in aqueous compositions exhibited less surfactant-rheology modifier interactions; that is, the fluorosurfactant content had less impact on the rheological properties of the aqueous composition than other surfactants, allowing for greater flexibility in adjusting the surface energy of the resulting sealing film, which was shown to have a significant impact on the sealing film performance. Specifically, as described above, improved performance was observed when a combination of a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer and a polyurethane was used, wherein the interfacial tension between the poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane was less than 2 mN / m. Furthermore, the inventors of the present invention were surprised to find that optimal performance was also observed when a combination of a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer and a polyurethane was used, wherein the polar component of the polyurethane surface energy was 10-20 mN / m.

[0140] These and other aspects of the present invention will be further understood upon consideration of the following examples, which are intended to illustrate certain specific embodiments of the present invention and are not intended to limit the scope of the present invention as defined by the claims. Example

[0141] Evaluation method of water-based sealing composition and sealing film

[0142] A. Preparation Example of Water-Based Sealing Composition:

[0143] A1. Example of Preparation of Carbon Black Dispersion. An aqueous solution of a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer containing 20 wt % of the polymer by volume of the solution is prepared. In one embodiment, the polymer is a poly(vinyl alcohol-co-ethylene) copolymer (Exceval TMRS-1717, supplied by Kuraray). That is, the solution contains 200 g of polymer per liter of solution. The carbon black powder is mixed with an aqueous solution of a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer. In one embodiment, an aqueous solution containing 106 g of a poly(vinyl alcohol-co-ethylene) copolymer is mixed with 162 g of carbon black ( 3500, supplied by Orion Engineered Carbon). The dispersion was mixed at 300 rpm for 30 minutes in an overhead mixer (Hei-torque value 200). The dispersion was then recirculated in a Generation 1Q1375 Flocell sonicator, where the sonicator jacket used cold water at 10°C and cooled at 100% amplitude for 3 hours and 23 minutes. The dispersion was continuously stirred until it was used to prepare the sealing composition.

[0144] A2. Preparation Example of Aqueous Sealing Composition In a container, the aqueous polyurethane dispersion is mixed with a wetting agent and an aqueous solution of a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer. In one example, 227.17 g of a 35 wt % aqueous polyurethane dispersion (L3838 aqueous dispersion, supplied by Hauthaway) is mixed with 683.2 g of an aqueous solution of a poly(vinyl alcohol-co-ethylene) copolymer (containing 20 wt % copolymer by volume of the solution). In this example, the poly(vinyl alcohol-co-ethylene) copolymer is Exeval supplied by Kuraray. TM RS-1717. The mixture was mixed at 90 rpm for 10 minutes using a Hei-Torque Value 200 overhead mixer. An appropriate amount of crosslinking agent was added and the mixture was mixed at 90 rpm for an additional 60 minutes. An appropriate amount of the carbon black dispersion prepared in A1 (0.530 L in one embodiment) was added and the resulting dispersion was mixed at 500 rpm for 60 minutes. The pH was then adjusted to 6.5-8.5 using ammonium hydroxide and the dispersion was mixed for an additional 30 minutes. An appropriate amount of rheology modifier was added dropwise to the dispersion and mixing continued for an additional 60 minutes. The dispersion was then degassed under reduced pressure (25 mmHg) for 5 days. Within 7 days of preparing the sealing composition, the resulting aqueous sealing composition was used to prepare a sealing film for the corresponding device.

[0145] B1. Example of preparing a sealing film using a drawdown method.

[0146] The sealing composition prepared in A2 above was coated on the indium tin oxide (ITO) side of the ITO-PET film using a Gardco drop coater. A gap of 15 mils and an eight-way square coater were used. The drop speed was set to 2 meters per minute, with a target of a dry film thickness of 30 + / - 2 μm. The coating was dried in an oven at 100°C for 15 minutes. The dried film was conditioned at 25°C and 55% RH for 24 hours.

[0147] B2. Example of preparing a sealing film using a roll-to-roll coating line.

[0148] In a roll-to-roll coating line, the sealing composition prepared in A2 above was coated on the indium tin oxide (ITO) side of the ITO-PET film using a slot die at a speed of 9 feet per minute at a dry thickness of 30 μm. The film passed through a conventional oven consisting of four heating zones at a speed of 9 feet per minute. The length of each heating zone was 5 feet. The temperature of the first zone was set to 80°C and the temperature of the remaining heating zones was set to 100°C. Once the dried sealing film on the ITO-PET passed through the drying oven, the film was cut into 3 sections, each about 24-30 inches long, and placed in a clean room controlled environment at a temperature of 25°C and a relative humidity (RH) of 55%.

[0149] C. Determination of the surface energy of the films.

[0150] The surface energy of the prepared sealing film was measured using a drop shape analyzer (Drop Shape Analyzer) provided by Kruss GmbH (as described in B1 above). Using a syringe with a needle, a 2.6 μL deionized water droplet was placed on the top surface of the sealing film, and the contact angle between the liquid (water) and the sealing film was measured. The measurement was repeated by replacing the water droplet with a diiodomethane droplet. The surface energy of the film was calculated by contact measurement using these two liquids with known surface energies. The contact angle measurement was repeated three times for each liquid (water and diiodomethane). After 5 seconds, 30 seconds and 55 seconds from the time when the droplet was placed on the sample film, the contact angle between the liquid and the top surface of the sealing film was measured using a high-resolution camera. Then, the total surface energy of each data point and its polar and dispersion components were calculated using the Owens, Wendt, Rabel and Kaelble (OWRK) method. The reported surface energy is the average of 9 data points (3 droplets × 3 time measurements).

[0151] D. Preparation of electro-optical devices.

[0152] An electro-optical device was prepared by filling a plurality of microcells with a mixture of charged pigment particles (white, cyan, magenta, and yellow) in Isopar E. The white and yellow particles were negatively charged, and the cyan and magenta particles were positively charged. An aqueous sealing composition was then applied to the openings of the microcells as described in B above. Figure 8 The device illustrated in the figure. The electro-optical device 800 includes, in order: a protective film 801, an optically transparent first adhesive layer 802, a substrate 803, a light-transmitting conductive layer 804, a bottom layer 805, a micro-unit layer 806, a sealing film 807, a second adhesive layer 808, an ITO electrode layer 809 and a glass layer 810. An electric field source 811 electrically connects the light-transmitting conductive layer 804 to the ITO electrode layer 809. A waveform is applied by the source to drive the desired optical state. The thickness of the first light-transmitting layer 802 is about 25 μm. The thickness of the substrate 803 is about 100 μm. The thickness of the bottom layer 1005 is about 0.4 μm. The micro-unit layer 806 includes a plurality of micro-units. The bottom thickness of each micro-unit is about 0.4 μm and the height is about 10 μm. The thickness of the sealing film 807 is about 10 μm, and the thickness of the second adhesive layer is about 4.5 μm.

[0153] E. Determination of interfacial tension of polymers.

[0154] For a particular combination of polymers, the interfacial tension between polymer 1 and polymer 2 is calculated from the surface tension values ​​(determined via the method described above in C). The interfacial tension between the two components is calculated by using the surface energy values ​​of each component and the following geometric equation:

[0155]

[0156] where σ ΑΒ is the interfacial tension between polymers A and B; σ Α is the total surface energy of polymer A; σ Β is the total surface energy of polymer B; σ A D and σ B D are the dispersion components of the surface energy of polymers A and B, respectively; σ A D and σ B D is the polar component of the surface.

[0157] Similarly, the interfacial tension between the sealing film and the adhesive layer can be measured.The adhesive layer standard comprises a polyurethane formed from an aqueous dispersion of a water-dispersible polyurethane.

[0158] F. Evaluation of the barrier properties of the sealing film against non-polar fluids.

[0159] An aqueous dispersion was prepared by mixing 10 grams of poly(vinyl alcohol) homopolymer or 10 grams of poly(vinyl alcohol-co-ethylene) copolymer and 10 grams of polyurethane in 100 ml of water. The dispersion was used as an aqueous polymer composition to form Fig. 9 The sealing film of the illustrated device 900. The sealing film is formed by the method described in B1 above. The device 900 includes, in order: a substrate 903, a light-transmitting conductive layer 904, a bottom layer 905, a microcell layer 906 and a sealing film 907. The microcells contain an electrophoretic medium containing white, black and red pigment particles in Isopar E. The device 900 is stored at 70°C for at least 24 hours. After this period of time, the electro-optical device is examined using an optical microscope for sagging of the sealing film due to loss of non-polar fluid from the electrophoretic medium. If the distance between the bottom of the microcavity being inspected and the lowest point of the bottom surface of the sealing film is less than 85% of the distance between the bottom of the microcavity and the highest point of the lower surface of the sealing film at the same microcell, the waterborne polymer composition is marked as "failed" for its barrier properties. Otherwise, that is, if the distance between the bottom of the microcell being inspected and the lowest point of the sealing film is 85% or more of the distance between the bottom of the microcell and the highest point of the bottom surface of the sealing film at the microcell being inspected, the sealed waterborne polymer composition is marked as "passed" for its barrier properties. For example, for the preparation of Fig. 10C The aqueous polymer composition of the illustrated electro-optical device is labeled "through" because the ratio of h2:h1 is 1 (no droop), and the aqueous polymer composition used to prepare Fig. 10D The waterborne polymer composition of the illustrated electro-optical device was labeled "failed" because the ratio of h2:h1 was 35% (the sag level exceeded 85%). Barrier property evaluation can also be performed qualitatively by observing the prepared electro-optical device through an optical microscope from the viewing surface of the device. Devices containing sealing films that sag severely have a significantly different appearance (non-uniform surface vs. uniform surface) than devices containing sealing films that have good barrier properties to non-polar fluids. For example, a device having a ratio corresponding to Fig. 10C The microunits ("vias") of the aqueous polymer composition of the sealing film are as Fig. 10A The results show that the uniformity of Fig. 10D In contrast, the aqueous polymer composition of the sealing film of Fig. 10B Table 3 shows the evaluation of various combinations of (1) poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and (2) polyurethane. Polymer 1 is a poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and Polymer 2 is a polyurethane. Details on the commercial materials of Polymer 1 and Polymer 2 can be found in Table 4.

[0160] G. Method for determining the thixotropic index of aqueous sealing compositions.

[0161] The thixotropic index (TI) is used to describe one aspect of the rheological behavior of waterborne sealing compositions. The thixotropic index is the viscosity ratio measured by a rheometer in a thixotropic loop test. The thixotropic loop test is performed by measuring the viscosity of the composition from low shear (10 -4 l / s) to high shear (10 3 l / s) and then in a second flow ramp (flow ramp 2) from high shear to low shear to generate a shear loop and measure the viscosity at different shear rates. The following equation is used to calculate 10 0 The thixotropic index of the viscosity value at a shear rate of l / s, where η(A) is the flow slope 1 at 10 0 The viscosity at l / s, η(B) is the flow slope 2 at 10 0 Viscosity in l / s.

[0162] TI=η(A) / η(B)

[0163] A high thixotropic index means that the fluid has a stronger shear-thinning behavior, while a low thixotropic index means that the fluid has a weaker shear-thinning behavior, closer to a Newtonian fluid. As shown in the experimental results below, the thixotropic index of the aqueous sealing composition is higher than 1.5, or 1.5 to 3, resulting in improved sealing film coating quality with lower defects (reduced dewetting and chattering).

[0164] H. Method for determining the HB rate index of a waterborne sealing composition.

[0165] The HB rate index (or Herschel-Bulkley rate index) is also used to describe the rheological behavior of aqueous sealing compositions. The shear stress of aqueous sealing compositions is determined for shear rates from 0 to 600 l / s. The Herschel-Bulkley parameters are fitted to the data and calculated by TRIOS software using the Herschel-Bulkley equation σ = σy + Kγ n Calculated, where σ is the shear stress, K is the consistency coefficient (viscosity), γ is the shear rate, n is the HB rate index, σ y is the yield stress. The HB rate exponent n quantifies the fluid behavior of the sealing fluid. If n < 1, the fluid has shear thinning behavior. If n > 1, the fluid has shear thickening behavior. If n = 1 and the yield stress (σ y ) is equal to zero, the fluid is Newtonian. TM A100 and HS1212) has better rheology modifier than ASE ( AS1130) and HEUR rheology modifier ( PU 1191, ACRYSOL TMRM-8W, 3300) lower HB rate index, the aqueous sealing composition containing ASE and HEUR rheology modifiers has improved coating quality (fewer defects).

[0166] I. Viscosity Ratio Method of Aqueous Sealing Compositions.

[0167] The viscosity ratio of the aqueous sealing composition was determined by obtaining a rheological curve for each aqueous sealing composition using a HR30 Discovery series rheometer from TA Instruments and a parallel plate sensor with a 40.0 mm diameter and a 1000.0 μm geometric gap, wherein the Peltier plate maintained the temperature at 25°C. A shear rate range of 10 -4 The viscosity of the aqueous sealing composition was measured by a flow ramp from 10 Hz to 1000 Hz, with two points taken every ten. The viscosity ratio was calculated as the low shear viscosity (at 10 - 3 l / s) divided by the high shear viscosity (at 10 3 That is, using the equation viscosity ratio = η (L) / η (H), where η (L) is the ratio of 10 -3 The viscosity at a shear rate of l / s, η(H) is 10 3 Viscosity at a shear rate of l / s.

[0168] J. Method for determining the coating quality of sealing films.

[0169] A front plane laminate comprising a microcell layer filled with an electrophoretic medium was coated with an aqueous sealing composition. The resulting board was cut into boards of about 32 inches in length and the coating quality was inspected. The board was placed on a surface under a fluorescent lamp (5000K fluorescent lamp) and the sealing film was visually inspected. The coating quality was determined based on four different quality defects such as dewetting, delamination, chatter, and turbid spot unevenness (CSM). Each sealing film was graded based on a grading system for each quality defect. Specifically, the defects were graded on a scale of 0 to 3, where 0 contained no defects and 3 contained the highest level of defects. That is, the larger the number, the worse the quality. Fig.11 Examples of sealing films corresponding to dehumidification graded systems are provided. Fig.12 Examples of sealing films corresponding to the layered grading system are provided. Fig.13 Examples of sealing films corresponding to the flutter grading system are provided. Fig.14 An example of a sealing film corresponding to the turbidity spot unevenness grading system is provided.

[0170] Dewetting occurs when the sealing fluid dewets from the filled microcell layer before drying is complete, leaving one or more spots where the sealing fluid is missing. Sealing films with more dewetting spots are given a higher dewetting rating. Sealing films with 1-2 spots receive a rating of 1, 3-5 spots receive a rating of 2, and 6 or more spots receive a rating of 3.

[0171] Delamination occurs when the dried sealing film separates / delaminates from the filled microcells. Plates with 2-5 small sized spots (less than 0.25 cm) receive a 1, plates with 5-10 small or medium sized spots (less than 1.25 cm) receive a 2, and sealing films with large spots (greater than 1.25 cm) or spots spread across their entire surface receive a 3.

[0172] Chatter describes the vertical lines that appear on the board. If the light is present but only visible at a specific light reflection angle, a grade of 1 is given. When the line is easily visible at all angles, a grade of 2 is given. If the line is dark and distinct, a grade of 3 is given.

[0173] Turbid Spots (CSM) are used to describe circular spots that often appear on the surface of sealing films. The size, shape and thickness of CSM vary depending on many factors including, but not limited to, sealing formula, electrophoretic medium and coating parameters. Light and / or small-sized (less than 0.25 cm) CSMs with no nucleation points in the center (small dark center points) are given a grade of 1. If nucleation is visible in the CSM, they are graded as 2. If the CSM, in addition to nucleation, is extremely coarse and / or large in size (greater than 1 cm), they are given a grade of 3.

[0174] Evaluation results

[0175] Unless otherwise indicated, the amounts of components in the compositions disclosed in the following tables are provided as percentages by weight of the components based on the weight of the composition excluding water. The term QS (sufficient amount) is used in some compositions to indicate the amount of water carrier. This means that the amount of water in the composition is as much as is required to make the composition 100%, but not more.

[0176] Unless otherwise indicated, if any residual or absorbed water or moisture is present in the sealing film, the disclosed amounts of sealing film components are calculated as weight % based on the weight of the component excluding the residual or absorbed water.

[0177] The example compositions whose numbers end with the letter F correspond to sealing film compositions, while the remaining example compositions correspond to water-based sealing compositions. The examples of sealing film compositions correspond to the same example numbers (with the suffix F) as the water-based sealing compositions used to prepare the sealing film compositions. Thus, Example 1F (sealing film composition) is prepared from Example 1 (water-based sealing composition).

[0178] Table 1A: Aqueous sealing compositions containing various rheology modifiers.

[0179]

[0180]

[0181] Table 1B: Sealing films formed from aqueous sealing compositions containing various rheology modifiers.

[0182]

[0183]

[0184] [1]Exceval TM RS-1717, provided by Kuraray.

[0185] [2] L3838 aqueous dispersion, supplied by Hauthaway as a 35% aqueous dispersion.

[0186] [3] 3500, courtesy of Orion Engineered Carbon.

[0187] [4] V-02-L2, supplied by Nisshinbo Chemical as a 40% aqueous solution.

[0188] [5]Solthix TM A-100, provided by Lubrizol.

[0189] [6] HS1212, supplied by BASF.

[0190] [7] AS1130, supplied by BASF.

[0191] [8] PU 1191, supplied by BASF.

[0192] [9]Acrysol TM RM-8W, supplied by Dow Chemical.

[0193]

[10] 3300, provided by Byk.

[0194]

[11] L-7607 copolymer, supplied by Momentive.

[0195] Table 2A: Aqueous sealing compositions containing various rheology modifiers and rheological measurements.

[0196]

[0197]

[0198] Table 2B: Sealing films and coating quality measurements formed from aqueous sealing compositions containing various rheology modifiers.

[0199]

[0200]

[0201] [1]Exceval TM RS-1717, provided by Kuraray.

[0202] [2] L3838 aqueous dispersion, supplied by Hauthaway as a 35% aqueous dispersion.

[0203] [3] 3500, courtesy of Orion Engineered Carbon.

[0204] [4] V-02-L2, supplied by Nisshinbo Chemical as a 40% aqueous solution.

[0205] [5]Solthix TM A-100, provided by Lubrizol.

[0206] [6] HS1212, supplied by BASF.

[0207] [7] AS1130, supplied by BASF.

[0208] [8] PU 1191, supplied by BASF.

[0209] [9]Acrysol TM RM-8W, supplied by Dow Chemical.

[0210]

[10] 3300, provided by Byk.

[0211]

[11] L-7607 copolymer, supplied by Momentive.

[0212] Table 2B shows that compared with the inclusion of a HASE rheology modifier such as Solthix TM Compared to the water-based sealing composition of A-1000, the HEUR rheology modifier such as The aqueous sealing composition of 3300 provides an improved coating quality of the corresponding sealing film. This can be demonstrated by the higher levels of corresponding turbid spot unevenness (CSM), dewetting, and chatter observed (Example 4, Example 7 and Example 8 relative to Comparative Example 5 and Comparative Example 9). The rheological properties of the aqueous sealing composition containing the HEUR rheology modifier are significantly different from the rheological properties of the aqueous sealing composition containing the HASE rheology modifier. Specifically, the improved sealing film is formed by such an aqueous sealing composition, which has (a) an HB rate index of 0.7 or higher, or 0.7 to 1, or 0.7 to 0.9 or 0.7 to 2, (b) a viscosity ratio of 7 or lower, or 1 to 7, or 2 to 7 or 0.5 to 7, and (c) a thixotropic index of 1.5 and higher, or 1.5 to 3. Similarly, the aqueous sealing composition containing the ASE rheology modifier (Example 1) shows similar rheological properties and provides a sealing film with good coating quality. Furthermore, it was observed that when the resolution was measured at 50°C, the image resolution of the display device having a sealing film formed from the aqueous sealing composition including the HEUR rheology modifier was superior to that of the display device having a sealing film formed from the aqueous sealing composition including the HASE rheology modifier.

[0213] Table 2C: Aqueous sealing compositions containing various rheology modifiers and surfactants.

[0214]

[0215]

[0216]

[0217] Table 2D: Sealing films formed from aqueous sealing compositions containing various rheology modifiers and surfactants.

[0218]

[0219]

[0220]

[0221] [1]Exceval TM RS-1717, provided by Kuraray.

[0222] [2] L3838 aqueous dispersion, supplied by Hauthaway as a 35% aqueous dispersion.

[0223] [3] 3500, courtesy of Orion Engineered Carbon.

[0224] [4] V-02-L2, supplied by Nisshinbo Chemical as a 40% aqueous solution.

[0225] [5]Solthix TM A-100, provided by Lubrizol.

[0226] [6] HS1212, supplied by BASF.

[0227] [7] AS1130, supplied by BASF.

[0228] [8] PU 1191, supplied by BASF.

[0229] [9]Acrysol TM RM-8W, supplied by Dow Chemical.

[0230]

[10] 3300, provided by Byk.

[0231]

[11] L-7607 copolymer, supplied by Momentive.

[0232]

[12] Capstone TM FS-31, provided by Chemours.

[0233]

[13] Capstone TM FS-3100, provided by Chemours.

[0234] Tables 2C and 2D disclose the inclusion of a rheology modifier (Solthix TMA-100) and various surfactants such as siloxane and fluorosurfactant compositions. In the case of siloxane-based surfactants, it is observed that the change in surfactant content in the formula causes a significant change in the viscosity of the aqueous sealing composition (see Example 2 relative to Example 13). On the contrary, the viscosity of the aqueous composition containing fluorosurfactants changes much less with the change in surfactant content (see Example 10 relative to Example 12). This phenomenon is not insignificant, because the surfactant makes it possible to adjust the surface energy of the aqueous sealing composition on the micro-unit layer, which affects the coating quality of the resulting sealing film. Therefore, it is feasible to use different surfactant contents to adjust the aqueous sealing composition to obtain a good coating quality of different micro-unit layers, improve wettability and minimize coating defects. Various surfactants interact differently with the rheology modifier of the aqueous composition. When there is a strong interaction between the surfactant and the rheology modifier, as observed when using the siloxane surfactant, a slight change in the surfactant content significantly changes the coatability and rheological curve, making it more sensitive to the operating formula window. That is to say, if the surfactant interacts strongly with the rheology modifier, it becomes infeasible to select a high content of surfactant and effectively control the surface energy and wettability of the aqueous sealing composition. The inventors of the present invention surprisingly found that aqueous sealing compositions containing fluorosurfactants show less variation in viscosity with varying surfactant content. Thus, the use of fluorosurfactants makes it possible to more easily optimize the rheological profile and the best coating quality.

[0235] Table 3 includes surface energy data for various polymer 1 materials, which are water-soluble poly(vinyl alcohol) homopolymers or poly(vinyl alcohol-co-ethylene) copolymers, and polymer 2 materials, which are polyurethanes. It also includes an evaluation of the barrier properties of each layer and calculations of the interfaces of various polymer combinations. The preparation methods of the corresponding polymer layers for the evaluation of barrier properties are described above in I. The determination of the surface energy (according to the method described in E above) was performed by first preparing and conditioning a sealing film from the corresponding aqueous composition containing only one polymer. The interfacial tension of each polymer combination was calculated from the surface energy data and the calculation method described in H above.

[0236] Table 3: Barrier properties of sealing films.

[0237]

[0238]

[0239]

[0240]

[0241]

[0242] Table 4: Table 3 Commercial materials used in the examples.

[0243]

[0244]

[0245] The interfacial tension data of polymer 1 and polymer 2 in Table 3 show that a sealing film comprising (a) a poly(vinyl alcohol) polymer or a poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%, and (b) a polyurethane in an aqueous carrier, wherein the interfacial tension between the two polymers (a) and (b) is less than 2 mN / m, forms a sealing film having good barrier properties to non-polar fluids.

[0246] The data in Table 3 also show that a sealing film made from an aqueous sealing composition comprising (a) a poly(vinyl alcohol) polymer or a poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%, and (b) a polyurethane in an aqueous carrier, wherein the polar component of the surface energy of the polyurethane is between 10 and 25 mN / m, forms a sealing film having good barrier properties to non-polar fluids.

[0247] Microscopic evaluation of polymer films prepared from the four aqueous sealing compositions prepared by the method described in B1 above showed a correlation between the uniformity of the film and the interfacial tension between the two polymers. Table 5 and Fig.15 The microscopic images of show that lower interfacial tension provides a more uniform polymer film. The improved compatibility obtained by the combination of polymers with smaller interfacial tensions may explain the improved barrier properties of the corresponding layers.

[0248] Table 5: Polymer films comprising a combination of poly(vinyl alcohol-co-ethylene) copolymers and polyurethanes having different interfacial tensions.

[0249]

[0250] Furthermore, it was observed during the study that aqueous sealing compositions comprising more than 70% by weight of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, based on the weight of the aqueous sealing composition excluding water, form sealing films that absorb significant amounts of moisture from the environment. This high hygroscopicity has a negative impact on the electro-optical performance of the display.

Claims

1. A sealing film, comprising: 15 to 60 weight percent, based on the weight of the sealing film, of a water-soluble poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer, wherein the poly(vinyl alcohol) homopolymer has a degree of hydrolysis of 90 to 99.5 percent, and wherein the poly(vinyl alcohol-co-ethylene) copolymer has a degree of hydrolysis of 90 to 99.5 percent and an ethylene content of less than 10 percent; 7 to 29 wt % polyurethane based on the weight of the sealing film; 0.05 to 10 wt % of a rheology modifier, based on the weight of the sealing film, wherein the rheology modifier is selected from the group consisting of a hydrophobically modified ethoxylated urethane and an alkali swellable emulsion polymer.

2. The sealing film of claim 1, further comprising 0.01 to 5 wt% of a surfactant based on the weight of the sealing film. The sealing film according to claim 2 , wherein the surfactant is a fluorine-containing surfactant.

4. The sealing film of claim 1, further comprising 5 to 70 wt% of carbon black based on the weight of the sealing film.

5. The sealing film of claim 1 further comprising 4.5 to 25 wt% of a water-soluble ether, based on the weight of the sealing film, the water-soluble ether having a molecular weight of 75 to 5000 Daltons and optionally comprising hydroxyl groups. The sealing film of claim 1 , wherein the total surface energy of the sealing film is less than 60 mN / m.

7. The sealing film of claim 1, wherein the interfacial tension between the water-soluble poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane is less than 2 mN / m.

8. An electro-optical device comprising: Conductive layer; a microcell layer comprising a plurality of microcells, each microcell comprising an opening, each microcell comprising an electrophoretic medium comprising charged particles in a non-polar carrier; The sealing film according to claim 1, wherein the sealing film spans the opening of each micro unit; an adhesive layer; and Electrode layer.

9. An aqueous sealing composition comprising: 15 to 60 wt. % of a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, based on the weight of the aqueous sealing composition excluding water, wherein the poly(vinyl alcohol) homopolymer has a degree of hydrolysis of 90 to 99.5%, and wherein the poly(vinyl alcohol-co-ethylene) copolymer has a degree of hydrolysis of 90 to 99.5% and an ethylene content of less than 10%; 7 to 29 wt % of a polyurethane, based on the weight of the aqueous sealing composition excluding water; 0.05 to 10 wt. % of a rheology modifier, based on the weight of the aqueous sealing composition excluding water, wherein the rheology modifier is selected from the group consisting of a hydrophobically modified ethoxylated urethane and a hydrophobically modified alkali swellable emulsion polymer; 0.01 to 5 wt % of a surfactant, based on the weight of the aqueous sealing composition excluding water; and 20 to 95 wt % water based on the weight of the aqueous sealing composition.

10. The aqueous sealing composition of claim 9, wherein the surfactant is a fluorine-containing surfactant.

11. The aqueous sealing composition of claim 9, further comprising 5 to 70 wt% of carbon black based on the weight of the aqueous sealing composition excluding water.

12. The aqueous sealing composition of claim 9, further comprising 1.0 to 40 wt% of a water-soluble ether, based on the weight of the aqueous sealing composition excluding water, the water-soluble ether having a molecular weight of 75 to 5000 Daltons and optionally containing a hydroxyl group.

13. The aqueous sealing composition of claim 9, further comprising 0.1 to 8 wt% of a polyurethane crosslinking agent based on the weight of the aqueous sealing composition excluding water.

14. The aqueous sealing composition of claim 13, wherein the polyurethane crosslinking agent is a polyisocyanate, a polyfunctional polycarbodiimide, a polyfunctional aziridine, a silane coupling agent, a boron / titanium / zirconium-based crosslinking agent or melamine formaldehyde.

15. The aqueous sealing composition of claim 9, wherein the aqueous sealing composition is -4 The viscosity of the aqueous sealing composition at a shear rate of 1 / s divided by the viscosity of the aqueous sealing composition at a shear rate of 10 2 The viscosity ratio of the viscosity at a shear rate of 1 / s is 7 or less.

16. The aqueous sealing composition of claim 9, wherein the aqueous sealing composition is -4 The viscosity of the aqueous sealing composition at a shear rate of 1 / s divided by the viscosity of the aqueous sealing composition at a shear rate of 10 2 The viscosity ratio of the viscosity at a shear rate of 1 / s is 1 to 7.

17. The aqueous sealing composition of claim 9, having an HB rate index of 0.7 or more.

18. The aqueous sealing composition of claim 9, having an HB rate index of 0.7 to 1.

19. The aqueous sealing composition of claim 9, which has a thixotropic index of 1.5 or more.

20. The aqueous sealing composition of claim 9, which has a thixotropic index of 1.5 to 3.

Citation Information

Patent Citations

  • Electrophoretic displays with improved high temperature performance

    US20040120024A1

  • Adhesive and sealing layers for electrophoretic displays

    US20040219306A1

  • Electrophoretic display

    US20150005720A1

  • Magnetophoretic display assembly and driving scheme

    US20150277160A1

  • Smart medication device

    US20160012710A1

Cited By

  • Method for synergistically optimizing performance of graphene oxide modified waterborne epoxy resin coating through rheology-curing

    CN121026879A